О Некоторых Аспектах Имущественных Правоотношений Ибадитов С Христианами = Sur certains aspects des relations de propriété des Ibadites avec les Chrétiens - Radivilov, Danylo (Восточная Европа в древности и средневековье: Экономические основы формирования государства в древности и средневековье : XXV Чтения памяти члена-корреспондента АН СССР В.Т. Пашуто и памяти чл.-кор. АН СССР А.П. Новосельцева Москва, 17-19 апреля 2013 г. Материалы конференции, 2013)

Экспедиция оманских ибадитов на Cокотру в хронике Тухфат ал-а‘йан би-сират ахл ‘уман = Expédition des Ibadites omanais à Socotra dans la Chronique de Tuhfat al-a’yan bi-sirat ahl 'uman - Radivilov, Danylo (XXVII Международная научная конференция по источниковедению и историографии стран Азии и Африки «Локальное наследие и глобальная перспектива», 2013)

Etat des connaissances et perspectives de recherche sur la dynastie des Banū Ḫaṭṭāb de Zawīla au Fezzân - Mouton, Jean-Michel (Quatrième journée sur la Libye antique et médiévale, 2013)

Les Zkara du Maroc: savoirs, croyances et pouvoirs, de l'orientalisme au développement - Planeix, Ariel (Université de Paris I-Panthéon Sorbonne, 2013)
Keywords: Zkaras -- Maroc

صورة الآخر في أدب الخوارج صراعهم مع الإمام علي بن أبي طالب (عليه السّلام) مثالاً - الساعدي, عباس عبيد (مجلة آداب المستنصرية, 2013)
مثل الآخر مشكلة في الرؤية الثقافية العربيّة لاسيّما عند التأصيل على الرغم من الموقف الحضاري للقرآن الذي شدد في كثير من سوره على ضرورة الالتقاء بالآخر ومحاورته ، بل ومشاورته والنزول عند رأيه إذا كان راجحاً…
Keywords: Kharijisme

قول الإمام علي في الخوارج (دراسة تحليلية) - تاج الدين, سكينة حسين كاظم (مجلة كلية التربية الأساسية للعلوم التربوية والإنسانية, 2013)
الخوارج في مروج المسعودي دراسة مقارنة
Keywords: Kharijisme

نظام العرّاسة ببلاد الحوايا: تراث نجع أم تاريخ مرحلة؟ - الحسين, الهاشمي (الثقافة الشعبية, 2013)
Keywords: Moeurs et coutumes

فريد غازي (1929-1962م) - المجمع التونسي للعلوم والآداب والفنون - بيت الحكمة (الموسوعة التونسية, 2013)
Keywords: Biographies -- Djerba -- 20e siècle

درغوث (1485-1565م) - المجمع التونسي للعلوم والآداب والفنون - بيت الحكمة (الموسوعة التونسية, 2013)
Keywords: Biographies

أحمد الدرجيني (600-670هـ/1204-1272م) - المجمع التونسي للعلوم والآداب والفنون - بيت الحكمة (الموسوعة التونسية, 2013)
Keywords: Biographies

سلبمان الحيلاتي (ق11هـ/17م) - المجمع التونسي للعلوم والآداب والفنون - بيت الحكمة (الموسوعة التونسية, 2013)
Keywords: Biographies -- Djerba -- 17e siècle

الشيخ إبراهيم الجمني (1037هـ-1134هـ/1628م-1721م) - المجمع التونسي للعلوم والآداب والفنون - بيت الحكمة (الموسوعة التونسية, 2013)
Keywords: Biographies

جربة - المجمع التونسي للعلوم والآداب والفنون - بيت الحكمة (الموسوعة التونسية, 2013)
Keywords: Djerba -- Histoire

سليمان الجادوي (1871-1951) - المجمع التونسي للعلوم والآداب والفنون - بيت الحكمة (الموسوعة التونسية, 2013)
Keywords: Biographies -- Djerba -- 20e siècle

صالح بن يوسف (1907-1961م) - المجمع التونسي للعلوم والآداب والفنون - بيت الحكمة (الموسوعة التونسية, 2013)
Keywords: Biographies -- Djerba -- 20e siècle

الجيلاني بن الحاج يحيى (1929-2010م) - المجمع التونسي للعلوم والآداب والفنون - بيت الحكمة (الموسوعة التونسية, 2013)
Keywords: Biographies -- Djerba -- 20e siècle

Le sultan sauve la mosquée de Roissy-en-Brie (Le Parisien, 2013)
C'est un pactole inespéré. Le sultanat d'Oman vient de verser 1,8 Mâ?¬ à une association de Roissy-en-Brie pour la construction du lieu de c
Keywords: Relations -- Oman -- France

المدرسة الجمنية: دراسة معمارية لنموذج من المعالم الرسمية بجبل مطماطة - بوخشيم, النوري (القيروان وجهتها: دراسات جديدة في الآثار والتراث. أعمال الندوة العلمية الدولية الثالثة لقسم علم الآثار (القيروان 1-4 أفريل 2009), 2013)

نشاط القنصلية الإيطالية في السلوم وأثره على حركة الجهاد الليبي (1922-1940م) - القائد, وفاء بلعيد ميلاد (سلسلة الدراسات التاريخية, 2013)
Italy; relations; Libya; politics and government; history

أغنيات البراءة - هيبه, عمر بن باحمد (المطبعة العربية, 2013)

‏شروق وغروب: سمفونية فكرية لم تكتمل - كوزي, طه بن إبراهيم (كتابك, 2013)

أعمالي في الثورة - بيوض, إبراهيم بن عمر (أيفي ميديا, 2013)
Keywords: Réformisme -- Mzab

‏السياسة النفطية الفرنسية في الجزائر (1952-1962) - بن عمر, موسى بن بكير (أيفي ميديا, 2013)
Keywords: Pétrole -- Algérie

‏صفحات من الكفاح ‏خاص بالشيخ بيوض الاستعمار الفرنسي في الجزائر - أبو العلا, محمد بن سليمان (أيفي ميديا, 2013)
Keywords: Bayyūḍ, Ibrāhīm ibn ʿUmar (1899-1981); Mouvement national -- Mzab

‏صفحات من الكفاح لمجاهد القرارة في الثورة التحريرية - أبو العلا, محمد بن سليمان (أيفي ميديا, 2013)
Keywords: Mouvement national -- Mzab

‏نشأت المذاهب الكلامية: فرقة الجهمية نموذجا - العوني, لمياء (مجمع الأطرش للكتاب المختص, 2013)
Keywords: Jahmiyya

‏رهانات الديني السياسي في مدينة غرداية فضاء عمومي أو فضاء جماعاتي؟ - المستاري, جيلالي; نوار, فؤاد (Les espaces publics au Maghreb: au carrefour du politique, du religieux, de la société civile, des medias et des NTIC = ‏الفضاءات العمومية في البلدان المغاربية: لقاء السياسي، الديني، المجتمع المدني والتكنولوجيات الحديثة للإعلام والاتصال, 2013)

‏إضاءات السنية في أهم مسائل الوصية: ضبط المفاهيم وتصحيح تصورات - الحاج موسى, بشير بن موسى (مؤسسة الشيخ عمي سعيد, 2013)
Keywords: Fiqh -- testament

‏العقود في المعاملات المالية - حمدي, محمد بن صالح (سلسلة الدين المعاملة, 2013)
Keywords: Fiqh -- Finance

الفتاوى: المعاملات - الخليلي, أحمد بن حمد (مكتبة الاجيال, 2013)
Keywords: Fatwas -- Oman -- 2000-....

الفتاوى: الوصية - الوقف - بيت المال - المساجد - مدارس القرآن - الأفلاج - الخليلي, أحمد بن حمد (مكتبة الاجيال, 2013)
Keywords: Fatwas -- Oman -- 2000-....

الفتاوى: الأيمان - الكفارات - النذور - الذبائح - الأطعمة - التدخين - الخليلي, أحمد بن حمد (مكتبة الاجيال, 2013)
Keywords: Fatwas -- Oman -- 2000-....

الفتاوى: الجنائر - حوادث المركبات - الخليلي, أحمد بن حمد (مكتبة الاجيال, 2013)
Keywords: Fatwas -- Oman -- 2000-....

الفتاوى: النكاح - الخليلي, أحمد بن حمد (مكتبة الاجيال, 2013)
Keywords: Fatwas -- Oman -- 2000-....

الفتاوى: العقيدة - الخليلي, أحمد بن حمد (مكتبة الاجيال, 2013)
Keywords: Fatwas -- Oman -- 2000-....

إشراقة أمل (مدرسة نوح عائشة, 2013)
Keywords: Enseignement -- Mzab; Périodiques -- Mzab

القوس والسهم قبل التاريخ في عمان : مواد الصناعة ومصادرها - الماحي, علي التجاني (أدوماتو, 2013)
Keywords: Archéologie -- Oman

الرسوم الصخرية في وادي الجفر بسلطنة عمان : الدلالة و المعنى - الجهوري, ناصر سعيد (أدوماتو, 2013)
Keywords: Archéologie -- Oman

‏ديوان سقوط قمم ومهازل أمم - دواق, سليمان بن عمر (المطبعة العربية, 2013)
Keywords: Poésie -- Mzab

En finir avec l’essentialisme à propos des événements du M’zab - Oussedik, Fatma; Ouali, Hacen (El Watan, 2013)
C’est devenu un infini feuilleton de violences. La moindre étincelle peut mettre le feu à Ghardaïa. Fatma Oussedik, auteure du livre Les Itifaqate, propose ici une analyse plus approfondie de la société mozabite.
Keywords: Conflits -- Mzab

Tiaret: Mémoire-miroir - Belkhodja, Amar (El Kalima éditions, 2013)

Ouargla : authenticité et élégance - Ferzouli, Mokhtar; Tazaïrt, Kamel; Idir, Kamal; Boudjadja, Nawal (Cdsp Editions, 2013)

اليد الدهبي: المرحومة عائشة بنت بكير امحمدي المعروفة باسم عيشة بوكر (1925-1996م) - ترشين, صالح بن عمر (سلسلة الأسفار المحترقة, 2013)
Keywords: Biographies -- Mzab -- 20e siècle

استشراف التجربة العمانية في جوادر: نحو خطاب النساني - البلوشي, خالد (جامعة نزوى, 2013)

مكتبة القطب في سطور هو بحث وصفي شامل لمكتبة القطب - سالمي, نور الدين بن بوعميد (مطبعة الآفاق, 2013)
Keywords: Bibliographie -- Mzab

علاقة إباضية وادي مزاب بالعثمانيين في إيالة الجزائر من خلال رسالة الشيخ أبي مهدي عيسى إلى يحي آغا - ناصر, بالحاج بن باحمد (المجلة التاريخية العربية للدراسات العثمانية, 2013)
يهدف هذا المقال إلى تبيين بعض حيثيات السياسة التي اتبعتها الإدارة الفرنسية اتجاه التنظيمات العثمانية للطوائف الحرفية والإثنية، بعد سقوط مدينة الجزائر في 05 جويلية 1830، هذه الطوائف التي لم تجد من جهتها خيارا غير التعامل مع الاحتلال الذي أصبح أمرا واقعا لا بد من التكيفّ معه، لكن زعاماتها وقعت في تناقضات كبيرة جراء الدور الجديد الذي أصبحت مجبرة على القيام به. وعندما لم تعد الإدارة بحاجة إلى هذه التنظيمات، نسفتها واستغنت عنها بشكل نهائي.

اداب اسلامية - الكندي, ماجد بن محمد (المؤلف, 2013)

وهكذا صلى رسول الله - بن معاد, منجي بن علي (منشورات التعارف, 2013)
Keywords: Pratiques rituelles

كتاب العبر وديوان المبتدأ والخبر في أيام العرب والعجم والبربر ومن عاصرهم من ذاوي السلطان الأكبر - ابن خلدون, عبد الرحمان بن محمد (القيروان للنشر, 2013)
Buch 2: Vorislamische Geschichte der Araber, Babylonier, Ägypter, Juden, Perser, Griechen, Römer, Goten u. a

أعلام من الذاكرة: الشيخ الطيب التليلي‏ ‏مسيرة وجهاد‏ - التليلي, محمود; السلامي, محمد الحبيب (مطبعة سوجيك, 2013)
Keywords: Biographies

نهضة الأعيان بحرية عمان - السالمي, عبد الله بن حميد (دار الكتاب المصري, 2013)

تحفة الأعيان في سيرة أهل عمان - السالمي, عبد الله بن حميد (مكتبة الإستقامة, 2013)

فجر العولمة الجديدة: مدخل معرفي وصفي وتأريخي إلى إشكاليات العلاقات الدولية المعولمة وإلى المساهمات الناقدة والمناهضة للعولمة الأخيرة والمتطلعة لعولمة بديلة - حجاج, قاسم بن حمو (دار نزهة الألباب للنشر والتوزيع, 2013)

Femme et famille en Tunisie : entre conservatisme et modernité - Bassalah, Safa (Faculté des sciences humaines et sociales de Tunis, 2013)
Keywords: Emigration -- Djerba -- Tunis

معالم الحضارة الإسلامية بوارجلان 296 - 626 هـ / 909 - 1229 م - بوعصبانة, عمر بن لقمان (دار نزهة الألباب, 2013)

البربر والإسلام - بوحجام, محمد بن قاسم ناصر (مكتبة الضامري, 2013)

مختارات من مقالات الشيخ أبي اليقظان في جريدة الأمّة - بوحجام, محمد بن قاسم ناصر (مؤسسة الشيخ أبي اليقظان الثقافية, 2013)
Keywords: Journalisme -- Mzab

قضايا الإصلاح الاجتماعي في مقالات جريدة الأمة لأبي اليقظان، ١٩٣٤-١٩٣٨‎ - جهلان, محمد بن أحمد (جمعية التراث, 2013)
Keywords: Journalisme -- Mzab

التعصبات المذهبية دعوها فإنها منتنة : الإسلام أمة واحدة - المعمري, محمد بن خليفه (مكتبة الجيل الواعد, 2013)

أبو اليقظان: و قواعد البناء و الإعداد و التربية - بوحجام, محمد بن قاسم ناصر (مؤسسة الشيخ أبي اليقظان الثقافية, 2013)

دور القواعد الفقهية في تطوير النظريات - التيواجني, مهني بن عمر (‏أعمال ندوة تطور العلوم الفقهية النظرية الفقهية والنظام الفقهي: ‏المنعقدة خلال عام 15-18 ‏جماد الأولى 1433هـ/7-10-4-2012م, 2013)

Homme à Si Jilani Bel Haj Yahya - Tmarzizet, Kamel (Séminaire Jilani Bel Haj Yahia - personnalités Djerbiennes (1ère édition) = ملتقى الجيلاني بالحاج يحيى لأعلام جربة (الدورة الأولى), 2013)
Keywords: Biographies -- Djerba -- 20e siècle

Un passionné de littérature - Younes, Ahmed (Séminaire Jilani Bel Haj Yahia - personnalités Djerbiennes (1ère édition) = ملتقى الجيلاني بالحاج يحيى لأعلام جربة (الدورة الأولى), 2013)
Keywords: Biographies; Biographies -- Djerba -- 20e siècle

جربة أجيم تحتفي بالباحث الجيلاني بن الحاج يحيى - قوجة, محمد (Séminaire Jilani Bel Haj Yahia - personnalités Djerbiennes (1ère édition) = ملتقى الجيلاني بالحاج يحيى لأعلام جربة (الدورة الأولى), 2013)

بلد بني يزقن من خلال المجتمع المدني - الحاج سعيد, يوسف بن بكير (مطبعة الآفاق, 2013)

الشامل في التجويد - بوسعدة, عمر بن أحمد (منشورات ألفا, 2013)

الفكر العقدي عند الإباضية حتي نهاية القرن الثالث الهجري - بن دريسو, مصطفى بن محمد (مكتبة الضامري, 2013)

Oman et la mer: une relation cinq fois millénaire (Ministère du Patrimoine et de la culture, 2013)

الخلاف الفقهي بين المالكية و الإباضية - الكاتب, عبد المحسن سالم (دار ابن حازم, 2013)

رواية ميمونة: ملحمة فتاة تتحدى ظلم إسرائيل وتروي أروع درس في الرشد والإيمان - بابا عمِي, محمد بن موسى (كتابك, 2013)

سمر أسرة مسلمة (العقيدة الإسلامية بأسلوب ميسر) - معمر, علي يحيى (جمعية التراث, 2013)

L'olivier porteur de mémoire et de valeurs d'usage - Ben Salah, Imed (Pensée méditerranéenne, 2013)

إمارة بنى وجيه 317 - 354 هـ / 929 - 965 م فى عمان - الدرويش, جاسم ياسين محمد (الوثيقة, 2013)

القضاء والقدر عند الإباضية والماتريدية - الشرقاوي, مصطفى إسماعيل عبدالرحيم (مجلة كلية الآداب, 2013)
Keywords: Religions comparées -- Ibadisme -- Mutazilisme

إسهامات علماء الإباضية في التفسير و علوم القرآن في القرنين الثالث عشر و الرابع عشر الهجريين دراسة تحليلية - المنذر, محمد سعيد (جامعة أم درمان الاسلامية, 2013)
Keywords: Coran -- Commentaires -- 9e siècle

الأباضية في اليمن عوامل الظهور ومبررات الاختفاء - مرشد, عمر محمد (التواصل, 2013)
Keywords: Ibadisme -- Yemen

Incidents de Ghardaïa: 14 personnes placées sous contrôle judiciaire (L'Expressiondz, 2013)
Keywords: Conflits -- Mzab

القواعد الفقهية عند الإباضية: دراسة نظرية تحليلية تأصيلية تطبيقية - أرشوم, مصطفى بن حمو (‏سلسلة القواعد الفقهية الإباضية, 2013)

القواعد الفقهية عند الإباضية: دراسة نظرية تحليلية تأصيلية تطبيقية - أرشوم, مصطفى بن حمو (‏سلسلة القواعد الفقهية الإباضية, 2013)

القواعد الفقهية عند الإباضية: دراسة نظرية تحليلية تأصيلية تطبيقية - أرشوم, مصطفى بن حمو (‏سلسلة القواعد الفقهية الإباضية, 2013)

الدليل الإحصائي للمساجد في سلطنة عمان - المعولي, أحمد بن محفوظ (وزارة الأوقاف والشؤون الدينية, 2013)
Keywords: Monuments -- Oman

تأملات الفحص الطبي في الزواج - الحراصي, سلطان بن محمد بن زهران (وزارة الأوقاف والشؤون الدينية, 2013)

أحكام القانون الدولي والعلاقات الدولية في الفقه الأباضي - أبو الوفا, أحمد (وزارة الأوقاف والشؤون الدينية, 2013)
Keywords: Droit -- Oman

أحكام القانون الدولي والعلاقات الدولية في الفقه الأباضي - أبو الوفا, أحمد (وزارة الأوقاف والشؤون الدينية, 2013)
Keywords: Droit -- Oman

مائة كتاب أباضي - إمام, محمد كمال الدين (وزارة الأوقاف والشؤون الدينية, 2013)
Keywords: Ouvrages de vulgarisation

مائة كتاب أباضي - إمام, محمد كمال الدين (وزارة الأوقاف والشؤون الدينية, 2013)
Keywords: Ouvrages de vulgarisation

الفتاوى: الجنائر - حوادث المركبات - الخليلي, أحمد بن حمد (وزارة الأوقاف والشؤون الدينية, 2013)
Keywords: Fatwas -- Oman -- 2000-....

الفتاوى: الأيمان - الكفارات - النذور - الذبائح - الأطعمة - التدخين - الخليلي, أحمد بن حمد (وزارة الأوقاف والشؤون الدينية, 2013)
Keywords: Fatwas -- Oman -- 2000-....

الفتاوى: الوصية - الوقف - بيت المال - المساجد - مدارس القرآن - الأفلاج - الخليلي, أحمد بن حمد (وزارة الأوقاف والشؤون الدينية, 2013)
Keywords: Fatwas -- Oman -- 2000-....

الفتاوى: المعاملات - الخليلي, أحمد بن حمد (وزارة الأوقاف والشؤون الدينية, 2013)
Keywords: Fatwas -- Oman -- 2000-....

الفتاوى: النكاح - الخليلي, أحمد بن حمد (وزارة الأوقاف والشؤون الدينية, 2013)
Keywords: Fatwas -- Oman -- 2000-....

الفتاوى: الصلاة - الزكاة - الصوم - الحج - الخليلي, أحمد بن حمد (وزارة الأوقاف والشؤون الدينية, 2013)
Keywords: Fatwas -- Oman -- 2000-....

الفتاوى: العقيدة - الخليلي, أحمد بن حمد (وزارة الأوقاف والشؤون الدينية, 2013)
Keywords: Fatwas -- Oman -- 2000-....

الفتاوى: العقيدة - الخليلي, أحمد بن حمد (وزارة الأوقاف والشؤون الدينية, 2013)
Keywords: Fatwas -- Oman -- 2000-....

بداية المجتهد ونهاية المقتصد مع الراجح من آراء المذهب الإباضي وفقه المذاهب الإسلامية - القرطبي, محمد بن أحمد بن رشد (في الفقه الإباضي المقارن, 2013)

بداية المجتهد ونهاية المقتصد مع الراجح من آراء المذهب الإباضي وفقه المذاهب الإسلامية - القرطبي, محمد بن أحمد بن رشد (في الفقه الإباضي المقارن, 2013)

بداية المجتهد ونهاية المقتصد مع الراجح من آراء المذهب الإباضي وفقه المذاهب الإسلامية - القرطبي, محمد بن أحمد بن رشد (في الفقه الإباضي المقارن, 2013)

بداية المجتهد ونهاية المقتصد مع الراجح من آراء المذهب الإباضي وفقه المذاهب الإسلامية - القرطبي, محمد بن أحمد بن رشد (في الفقه الإباضي المقارن, 2013)

بداية المجتهد ونهاية المقتصد مع الراجح من آراء المذهب الإباضي وفقه المذاهب الإسلامية - القرطبي, محمد بن أحمد بن رشد (في الفقه الإباضي المقارن, 2013)

بداية المجتهد ونهاية المقتصد مع الراجح من آراء المذهب الإباضي وفقه المذاهب الإسلامية - القرطبي, محمد بن أحمد بن رشد (في الفقه الإباضي المقارن, 2013)

بطين لمحات عنها: تذكرة للأجيال القادمة - الفلاحي, أحمد (الرؤيا للصحافة والنشر, 2013)

Tifidellas - Ben Maamar, Fathi (Ifsan n tamunt : tullisin n tmurt tmazga, 2013)
Keywords: Littérature -- Djerba

Ifsan n tamunt : tullisin n tmurt tmazga - Metmati, Samail (Tira éditions, 2013)
Keywords: Littérature -- Mzab

واقع السياحة في مدينة يفرن - عمران, هدى محمد (مجلة الجامعة, 2013)
Keywords: Tourisme -- Djebel Nefousa

معالم السيرة النبوية: رؤية تحليلية و نظرة تصحيحية - السيابي, أحمد بن سعود (مكتبة الضامري, 2013)

العريف ودوره التعليمي والتربوي في النظام التعليمي عند إباضية المغرب الأوسط - زيدور, عبد الحميد (مجلة الناصرية للدراسات الاجتماعية والتاريخية, 2013)
سوف نحاول أن نتعرض إلى نظام العزابة من وجهة الجانب التعليمي والتربوي، وبالخصوص العريف ودوره التعليمي على اختلاف أصنافه ومسؤولياته. وبداية لمعرفة طبيعة المذهب الاباضي في المغرب الإسلامي التي فرضت نظام العزابة لابد من توضيح بعض الأمور الخاصة بمسالك الدين عند الاباضية باعتبارها قاعدة أساسية في تحصين الفكر المذهبي من الفناء، ثم نتدرج إلى المجتمع المزابي الذي تبنى المذهب واخلص له في إطار نظام العزابة. وأخيرا التركيز على هيئة محددة بوضوح يمثلها العريف ودروه التعليمي والتربوي في الحفاظ على الهوية الاباضية.
Keywords: Enseignement -- Afrique du Nord -- Moyen-âge

العلاقات العمانية الفرنسية في عهد السيد سعيد بن سلطان - العثمان, باسمة عبد العزيز عمر (مجلة التربية والعلم, 2013)
Keywords: Relations -- Oman -- France

Otantik Bir Vehbi-İbâzî Akaîd Metni: Akidetü't-Tevhid Li-Amr İbn Cümey - Dündar, M. (KADER Kelam Araştırmaları Dergisi, 2013)
Ib?diyya is the only branch of Kh?rijiyya which rejects “isti ? r?d” and have a more moderate disposition by not qualifying their opponents as disbelievers (mushrik). As one of the most ancient creed text that had been originally authored in Tamazight, ? Aq?da al-Tawh?d, is a work that shows us the fundamental beliefs of Maghreb Ib?d?s and their distinctive features in concise style. The text that its Tamazight origin could be dated back to third century of hijra was translated into Arabic by Ib?d? scholar ? Amr ibn Jumay ? in late seventh or early eighth century of hijra. In this study, it has been attempted to make an annotated Arabic edition of this neglected piece in History of Sects by comparing the old edition of it and the text in the its published commentary. Also its translation into Turkish and some assessments on the text has been undertaken. In annotations, Ib?d? references, heresiographies and the commentary of the text have been taken into account.
Keywords: Foi -- Traité

الوقف الثقافِي للمغاربةِ في مصر العثمانيةِ من خلال سجلات المحاكم الشرعيّة تجربة أهل جربة وأهل فاس في القرن 12هـ/18م - مصلح, أحمد بن مهني (جامعة ﻣﺤمد اﻟﺨامس, 2013)
Keywords: Waqf (fondations) -- Djerba

التعارف - البهلوي, أبي محمد عبد الله بن محمد (ذاكرة عمان, 2013)

حاشية سليمان الجربي على مختصر التفتازاني للسيخ سليمان بن عبد الحمن بن سليمان المغربي الجربي السمومني الشهير بسليمان الجربي (و 885هـ/1480م - ت 966هـ/1558م) دراسة وتحقيق - حاج أمحمد, يحيى بن بهون (جامعة الجزائر, 2013)

المشرق العربي من خلال جريدة الأمة لأبي اليقظان 1352-1357هـ/1933-1938م - الرزقي, خيري (جامعة الجزائر 2, 2013)

خصوصيات العمران الصحراوي - دراسة حالة مدينة غرداية - الأغواطي, محمد عبد الوهاب (جامعة عمار ثليجي, 2013)
Keywords: Urbanisme -- Mzab

مسائل التحقيقية في بيان التحفة الأجرومية للشيخ امحمد بن يوسف اطفيش تحقيق ودراسة - حيدرة, رشيد (جامعة السانيا, 2013)
Keywords: Atfiyyash, Muhammad b. Yusuf (1821-1914)

دور المجتمع المدني في تجسيد الحكم الراشد بولاية غرداية - باعلي وسعيد, باحمد بن صالح (جامعة الجزائر 3, 2013)

الحياة الاجتماعية والثقافية بوارجلان ونواحيها خلال القرنين 5-6هـ/11-12م - حمامد, محمد (جامعة أحمد دراية, 2013)

ملحق السير الشماخي من رجال 950هـ إلى رجال1350 هـ لمؤلفه أبي اليقظان إبراهيم دراسة وتحقيق: القسم الخاص بأعلام القرنين العاشر والحادي عشر الهجريين / السادس عشر والسابع عشر الميلاديين - كروشي, نور الدين (جامعة قسنطينة 2, 2013)
Keywords: Prosopographie -- Afrique du Nord

آراء الخوارج الكلامية: الموجز لأبي عمار عبد الكافي الأباضي - عبد الكافي, أبو عمّار (موفم للنشر, 2013)
Keywords: Foi -- Traité -- 12e siècle

النظام الإداري في عمان خلال الفترة من القرن 6هـ/12م- 10هـ/16م - الخروصي, عبد العزيز بن هلال (جامعة الجزائر 2, 2013)

التنافس الدولي على مضيق هرمز وأثره على سيادة سلطنة عمان - الحجري, عامر بن محمد بن شامس (جامعة لاهاي, 2013)
Keywords: Politique étrangère -- Oman

السهل والميسر في تعلم اللغة الأمازيغية : محادثة بلهجة غدامس - هارون, أبو بكر (دار الفرجاني, 2013)
Keywords: Linguistique

Les waqfs aujourd'hui chez les Ibadites mozabites d'Algérie - Tounsi, Slimane (L'économie des waqf-habous : des modalités de possession des propriétés en waqf aux réseaux internationaux des bénéficiaires en terre d‟islam et au-delà, 2013)
Keywords: Waqf (fondations) -- Mzab

القبس في علم التجويد - القنوبي, عبد الله بن سعيد (مكتبة و تسجيلات البدر, 2013)

عبد الرحمان بن رستم الفارسي (توفي 258 للهجري) دراسة وتعليق - البوجديدي, علي (الحياة الثقافية, 2013)
Keywords: Dynastie rustumide

في السيرة المسورية البكرية - تغلات, زهير (الحياة الثقافية, 2013)
Keywords: Ibadisme -- Djerba

المستظهرون لكتاب الله العزيز بالقرارة (1433 1434 / 2012 2013) (الحياة, 2013)

إصلاح ذات البين وتجربة المجتمع الميزابي الإباضي في الجزائر (الحلقة الأولى) - أبو بكر, صالح بن عبد الله (الحياة, 2013)

القواعد الفقهية عند الإباضية - ارشوم, مصطفى بن حمو (الحياة, 2013)
Keywords: Fiqh

الشيخ سالم بن يعقوب، حياة رجل وتجربة جيل (الحلقة الثانية) - البوجديدي, علي (الحياة, 2013)

تحية الوفاء لوادي العطاء - التندميرتي, عمرو أحمد (الحياة, 2013)
Keywords: Poésie -- Djebel Nefousa

من وحي « أماه» للشهيد المغيب عمرو النامي، منه إليه - التندميرتي, عمرو أحمد (الحياة, 2013)

الحاج محمد بن عيسى بن عمارة خبزي 1927-2013 - الشيخ بالحاج, عيسى بن محمد (الحياة, 2013)
Keywords: Biographies -- Mzab -- 20e siècle

الشيخ بيوض إبراهيم بن عمر وبناء الشخصية العلميَّة - الشيخ بالحاج, عيسى بن محمد (الحياة, 2013)
Keywords: Bayyūḍ, Ibrāhīm ibn ʿUmar (1899-1981)

الرواية عند الإباضية وقاعدتي العرض على القرآن وعمل المسلمين مدونة أبي غانم الخراساني أنموذجا - العبري, بدر بن سالم (الحياة, 2013)
Keywords: Fiqh -- Libye -- 8e siècle

سلام نفوسة - المعولي, زياد بن طالب (الحياة, 2013)
Keywords: Poésie -- Oman

ولاية المرأة القضاء بين الفقه الإسلامي والقانون الوضعي - الوهيبي, خالد بن مبارك (الحياة, 2013)
Keywords: Fiqh

القرآن أساس التجديد والاجتهاد، الشيخ بيوض إبراهيم نموذجا - باجو, مصطفى بن صالح (الحياة, 2013)
Keywords: Bayyūḍ, Ibrāhīm ibn ʿUmar (1899-1981); Ijtihad -- Mzab -- 20e siècle

اللغة العربية ودورها في تنمية الذوق الأدبي (الحلقة الأولى) - بوحجام, محمد بن قاسم ناصر (الحياة, 2013)

الترسل الأدبي في البيت الرستمي، مقاربة أسلوبية - بوصوري, ناصر (الحياة, 2013)

العلامة أبو صفرة عبد الملك بن صفرة وكتابه «الجامع» - بولرواح, إبراهيم بن علي (الحياة, 2013)

الأطروحات الناقدة والمناهضة للعولمة الأخيرة.... - حجاج, قاسم بن حمو (الحياة, 2013)

الافتتاحية - حدبون, صالح بن أحمد (الحياة, 2013)

فقه المال العام عند الإباضية: فقه المال العام من خلال كتاب «المصنف» - حمدي, محمد بن صالح (الحياة, 2013)
Keywords: Fiqh

البعثة العلمية الميزابية بتونس: أهداف وعوائق - حمودة, مصطفى بن بكير (الحياة, 2013)

سيرة الأجداد - زقاو, نانة بنت محمد (الحياة, 2013)

نظرية الربا، التماسك والاضطراب - شخار, أبو نصر بن محمد (الحياة, 2013)

ثنائية العنف والرقة في القصيدة الثورية الجزائرية ديوان أطلس المعجزات لصالح خرفي القراري الجزائري نموذجا - عبد اللطيف, حني (الحياة, 2013)
Keywords: Poésie -- Mzab

اليوبيل الذهبي، (الذكرى الخمسون لاستقلال الجزائر) - لزعل, أحمد موسلمال (الحياة, 2013)

Looking at the Kitab-i Bahriye of Piri Reis - Lepore, Fortunato; Piccardi, Marco; Rombai, Leonardo (e-Perimetron, 2013)
Keywords: Cartes -- Djerba

‏الفتح المغيث في علوم الحديث - المطوع, محمد بن سليمان (مكتبة الضامري, 2013)

Djerba retient son souffle (Jeune Afrique, 2013)
Keywords: Judaïsme -- Djerba

«Il y a une politique d'Etat programmée pour effacer l'identité mozabite» - Benfodil, Mustapha (El Watan, 2013)
- D'abord, qu'est-ce qui a déclenché, selon vous, ces événements qui ont ébranlé Ghardaïa ? Je note d'emblée que les gens ne cherchent que le sensationnel. «Combien y a ...
Keywords: Fekhar, Kamel Eddine (1963-2019)

A Ghardaïa, c'est le pourrissement... - Benfodil, Mustapha (El Watan, 2013)
Une lourde tension pesait hier sur Ghardaïa après les affrontements intercommunautaires. Certains commerces ont ouvert, mais les deux camps s'observent malgré les appels au calme. La ville était toujours quadrillée ...
Keywords: Fekhar, Kamel Eddine (1963-2019)

Abdelmalek Sellal aujourd'hui dans la wilaya de GhardaïaUne visite sous haute tension - Bensouiah, Azzeddine (Liberté (Algérie) (site web), 2013)
Le Premier ministre se rend, aujourd'hui, dans le chaudron ghardaoui pour une visite pas comme les autres. La wilaya, qui vit au rythme de conflits communautaires, connaît un regain de ...
Keywords: Fekhar, Kamel Eddine (1963-2019)

Des blessés et des arrestations dans des émeutes à Ghardaïa - Azzoug, Farid (El Watan, 2013)
L'inauguration de la traditionnelle Fête du tapis prévue hier à Ghardaïa a dégénéré en émeute suite à l'organisation d'un sit-in citoyen initié par le bureau local de ...
Keywords: Fekhar, Kamel Eddine (1963-2019)

Il revient de manière cyclique depuis une vingtaine d'années Ghardaïa : au coeur d'un conflit intercommunautaire - Kebir, Karim (Liberté (Algérie) (site web), 2013)
Ghardaïa, jadis havre de paix et destination de prédilection des touristes en mal d'exotisme, est entrée dans une spirale de violences cyclique. Pourquoi ? Comment ? Éléments de réponse. "J'ai dit ...
Keywords: Fekhar, Kamel Eddine (1963-2019)

Algérie : les autorités veulent ramener le calme dans le Sud (L'Orient-Le Jour, 2013)
Le ministre algérien de la Communication Abdelkader Messahel a évoqué samedi une prochaine "initiative" des autorités pour mettre un terme définitif aux tensions dans la région de Ghardaïa, dans le sud ...
Keywords: Fekhar, Kamel Eddine (1963-2019)

MAK : la tragédie du peuple mozabite à Ghardaïa (Le Matin DZ (site web), 2013)
Le Mouvement de l'autonomie de la Kabylie a rendu public un communiqué pour dénoncer l'agression dont est victime le peuple mozabite. Ghardaïa vit dans la peur Le peuple mozabite ...
Keywords: Fekhar, Kamel Eddine (1963-2019)

Plusieurs dizaines de blessés et des magasins incendiés dans des affrontements intercommunautaires Déchaînement de violence à Ghardaïa - Kebir, Karim (Liberté (Algérie) (site web), 2013)
On ne reconnaît plus la ville de Ghardaïa, "pentapole du désert", chantée par Michel Sardou au milieu des années 80, jadis havre de paix et mecque des téméraires touristes occidentaux. Aujourd ...
Keywords: Fekhar, Kamel Eddine (1963-2019)

Répression policière à Ghardaïa : votre silence nous tue ! (Le Matin DZ (site web), 2013)
Dans quel pays vit-on ? De quelle race sont ses criminelles qui nos gouvernent ? Kameleddine Fekhar Répression policière à Ghardaïa : http://www.youtube.com/watch?v=DECRFe9vZzs&feature=youtu.be ...
Keywords: Fekhar, Kamel Eddine (1963-2019)

Situation à Ghardaïa : appel de détresse urgent (Le Matin DZ (site web), 2013)
Jadis paisible cité commerciale et touristique, Ghardaïa est devenue depuis quelques jours le centre d'affrontemens communautaires entre les Mozabites et la communauté arabe. Nous publions l'appel de détresse de ...
Keywords: Fekhar, Kamel Eddine (1963-2019)

Les conflits intercommunautaires risquent de reprendre à tout moment Ghardaïa : la vieille ville quadrillée par les forces antiémeutes - Kachemad, L. (Liberté (Algérie) (site web), 2013)
Un grand renfort de forces antiémeutes est arrivé de Boufarik, de Khenchela et d'Alger et a pris possession des points névralgiques de la vieille ville. C'est une ville en ...
Keywords: Fekhar, Kamel Eddine (1963-2019)

Ils ont éclaté hier en début de soirée Troubles à Ghardaïa (Liberté (Algérie) (site web), 2013)
Des troubles ont éclaté hier en début de soirée au centre-ville de Ghardaïa, à proximité du quartier commercial, a-t-on appris de source locale. Selon le Dr Kamel-Eddine ...
Keywords: Fekhar, Kamel Eddine (1963-2019)

K. Fekhar : "La justice algérienne est au service du pouvoir exécutif et des corps sécuritaires (Le Matin DZ (site web), 2013)
Dr Kameleddine Fekhar, est journaliste indépendant et militant pour la démocratie. Il est aussi activiste pour la défense des droits humains et Algérien appartenant à la minorité Mozabite. Il vient d ...
Keywords: Fekhar, Kamel Eddine (1963-2019)

Ghardaïa Kamel-Eddine Fekhar condamné à une année de prison ferme - Kachemad, L. (Liberté (Algérie) (site web), 2013)
Deux semaines après le procès, qui s'est déroulé le mardi 19 novembre au tribunal de Ghardaïa et au cours duquel le procureur de la République près le même tribunal avait ...
Keywords: Fekhar, Kamel Eddine (1963-2019)

Kamel Eddine Fekhar condamné à un an de prison ferme - Nazim, K. (El Watan, 2013)
Une année de prison ferme a été prononcée hier par le tribunal de Ghardaïa contre Kamel Eddine Fekhar, le responsable de la section locale de la Ligue algérienne de défense des ...
Keywords: Fekhar, Kamel Eddine (1963-2019)

Arrêtez ces crimes contre l'humanité et la torture dans le Mzab ! (Le Matin DZ (site web), 2013)
de la police avec les arabes qui agressaient les mozabites sans arrêter aucuns d'eux: http://www.youtube.com/watch?v=uBk8IInWssQ&sns=fb 2- une vidéo des évènements de Berriane 2008 qui montre La cohésion et de la coopération ...
Keywords: Fekhar, Kamel Eddine (1963-2019)

Appel à la solidarité avec des prisonniers mozabites à Ghardaïa (Le Matin DZ (site web), 2013)
violence sans justification etsans aucun avertissement au préalable, malgré le pacifisme de sit-in, comme le montre cette vidéo prise le 26/03/2013 à 08 heure 45 du matin : http://www.youtube.com/watch?v=pGUKP6RDFJM ...
Keywords: Fekhar, Kamel Eddine (1963-2019)

Algérie: 6 policiers blessés lors d'affrontements communautaires dans le Sud (AFP, 2013)
Au moins six policiers ont été blessés et quatre personnes arrêtées lors d'affrontements entre deux communautés rivales à Ghardaïa (sud), ont indiqué mardi une source policière et un militant des ...
Keywords: Fekhar, Kamel Eddine (1963-2019)

Le voyage de noces en Tunisie vire au cauchemar pour un couple de Beaurinois - Féret, Hubert (La Voix du Nord, 2013)
Des chambres insalubres, une climatisation en panne, une électricité défectueuse voire dangereuse, des cuisiniers qui rendent leur tablier, une piscine à l'eau trouble, avec qui plus est une suspicion de présence de légionelle. Puis un hôtel qui ferme, purement et simplement, avec des vols et des scènes de pillage à la clé, et près de deux cents vacanciers qui ne savent plus à quel saint se vouer. Le voyage de noces au complexe Dar Djerba Marmara d'un jeune couple de Beaurinois, Pauline et Dimitri Fevin, a viré au cauchemar. Ils racontent... La dame de chez Auchan Voyages n'avait eu jusqu'ici que des «retours positifs». Et à lire les commentaires des internautes sur des sites comme Tripadvisor, Pauline et Dimitri n'en doutaient pas. À ce jeune couple tout juste marié, c'est sûr, le complexe Dar Djerba Marmara (groupe TUI), en Tunisie, allait laisser un souvenir im-pé-ris-sa-ble! C'est le cas. Mais pas vraiment dans le sens positif du terme...
Keywords: Tourisme -- Djerba

Chasse des militants des droits humains de Ghardaïa (Le Matin DZ (site web), 2013)
Le pouvoir ne relâche pas la pression sur les militants des droits de l'Homme à Ghardaïa. Ghardaïa, la paisible, est livrée aux baltaguia Après l'échec du plan primitif du ...
Keywords: Fekhar, Kamel Eddine (1963-2019)

Algérie: plusieurs blessés dans des heurts entre deux communautés rivales (AFP, 2013)
Plusieurs personnes ont été blessées ces derniers jours dans des affrontements entre deux communautés rivales à Ghardaïa, à 600 km au sud d'Alger, ont indiqué mardi un militant des droits ...
Keywords: Fekhar, Kamel Eddine (1963-2019)

Le pouvoir algérien s'acharne sur la minorité mozabite (Le Matin DZ (site web), 2013)
Lundi 6 mai 2013, la population mozabite de la ville de Malika ont vécu une deuxième nuit consécutive d'horreurs, leurs maisons ont été attaquées pendant plusieurs heures par des bandes ...
Keywords: Fekhar, Kamel Eddine (1963-2019)

Alors qu'une cinquantaine de militants de la LADDH ont organisé un sit-in de soutien Kamel Eddine Fekhar et ses 7 compagnons repassent devant le magistrat instructeur - Kachemad, L. (Liberté (Algérie) (site web), 2013)
Une semaine après avoir été remis en liberté provisoire -- après que la Chambre d'accusation près le tribunal de Ghardaïa eut annulé la décision de la juge d'instruction qui avait ...
Keywords: Fekhar, Kamel Eddine (1963-2019)

Algérie: libération de 8 personnes incarcérées après des manifestations (ONG) (AFP, 2013)
Huit personnes incarcérées à la suite de violents affrontements entre policiers et jeunes chômeurs à Ghardaïa (sud) ont été libérées mardi, a-t-on appris mercredi auprès de la Ligue algérienne ...
Keywords: Fekhar, Kamel Eddine (1963-2019)

Ghardaïa Liberté provisoire pour le Dr Kamel Eddine Fekhar et ses sept compagnons - Kachemad, L. (Liberté (Algérie) (site web), 2013)
Après être repassés mardi soir devant la chambre d'accusation près le tribunal de Ghardaïa, Kamel Eddine Fekhar et ses sept compagnons, placés mercredi dernier sous mandat de dépôt par le ...
Keywords: Fekhar, Kamel Eddine (1963-2019)

Après les affrontements qui ont émaillé l'ouverture de la fête du tapis 8 personnes sous mandat de dépôt à Ghardaïa - Kachemad, L. (Liberté (Algérie) (site web), 2013)
C'est mercredi, tard dans la soirée, que les 18 prévenus arrêtés lors des affrontements entre forces de l'ordre et militants des droits de l'Homme (Laddh) ont été présentés ...
Keywords: Fekhar, Kamel Eddine (1963-2019)

Le dialogue de sourds continue - M., Aziz (El Watan, 2013)
A défaut de dialoguer, les autorités ont choisi la brutalité face au mouvement de protestation du Sud, comme l'ont démontré les troubles à Ghardaïa et l'emprisonnement de militants. Les ...
Keywords: Fekhar, Kamel Eddine (1963-2019)

Alors que des membres du CNDDC d'El-Oued sont arrêtés puis relâchés Calme précaire à Ghardaïa après les affrontements de la veille (Liberté (Algérie) (site web), 2013)
Coïncidant avec la Fête du tapis dans la vallée du M'zab, de violents affrontements ont opposé des jeunes aux éléments des unités antiémeutes de la sûreté de wilaya de Ghardaïa ...
Keywords: Fekhar, Kamel Eddine (1963-2019)

La tension persiste dans le Sud - Makedhi, Madjid (El Watan, 2013)
Le Sud continue à bouillonner. La tension persiste et tend à se généraliser. Près de quinze jours après la démonstration de force des jeunes chômeurs de Ouargla, la mobilisation ne faiblit ...
Keywords: Fekhar, Kamel Eddine (1963-2019)

Ghardaïa retrouve son calme - Makedhi, Madjid (El Watan, 2013)
Retour au calme à Ghardaïa. Après une vive tension engendrée par des affrontements entres jeunes des deux communautés, mozabite et arabophone, la ville a repris son rythme de vie habituel hier ...
Keywords: Fekhar, Kamel Eddine (1963-2019)

le conflit tribal resurgit à Ghardaïa - Makedhi, Madjid (El Watan, 2013)
Selon le responsable de la LADDH à Ghardaïa, des jeunes du quartier Hadj Messaoud (à majorité arabophone) se sont attaqués à des habitations et des édifices publics du quartier Melika (à ...
Keywords: Fekhar, Kamel Eddine (1963-2019)

Pourquoi Marmara rouvre le Dar Djerba... a minima (L'Echo touristique, 2013)
Keywords: Tourisme -- Djerba

Marmara : la réouverture du Dar Djerba est repoussée sine die (L'Echo touristique, 2013)
Keywords: Tourisme -- Djerba

al-Sulṭā tughlaq Jāmaʿ Malāq bi-Wālagh fī intiḍār hasm al-nizāʿ qānūniyyan bayn al-mutanāziʿīn ʿalayha min al-Ibāḍiyyīn wa Salāfiyyīn - Jarīrī, ʿAbd al-Ḥalīm al- (al-Jazira, 2013)
Keywords: Malāq, mosquée (Oualegh, Djerba)

Minorities in North Africa: George Joffé traces the history of the Ibadi and Jewish communities - Joffé, E. George H. (The Middle East in London, 2013)

al-Multaqā al-Awwal li-ʿAmmī Saʿīd al-Khayrī al-Jarbi, Taḥt al-shirāʿ : « ʿammī Saʿīd al-Jarbi bayn Jarba wa Mīzāb : Jusur madīd li-Tajarba Iṣlāḥiyya rāʾida - الباروني, سعيد بن يوسف (al-Jazira, 2013)

Ḥaqīqat mā Jarā fī Jāmaʿ Malāq - Abū Riyāḍ (al-Jazira, 2013)
Keywords: Malāq, mosquée (Oued Zbib, Djerba); Monuments -- Djerba

جربة زوايا نظر - البوجديدي, علي; يامون, مسعود (الحياة الثقافية, 2013)

Jarba, Sanaghāfūr al-Mutawāsiṭ, lam lā ? wa mā ladhī yamnaʿ - Shtūrū, Shams al-Dīn (al-Jazira, 2013)

Qirāʾat min kitāb « Tārīkh Jarba wa ʿulamāʾihā ». Tahlīf al-Shaykh Sālim b. Yaʿqūb - Ibn Yaʿqūb, Nājī (al-Jazira, 2013)
Keywords: Recension

al-Zaʿīm ʿAlī al-Zlīṭnī - Zlīṭnī, Muḥammad Ḥāfiẓ (al-Jazira, 2013)
Keywords: Biographies; Biographies -- Djerba -- 20e siècle

Quelques exemples de reconversion (Archibat, 2013)
Keywords: Architecture -- Djerba

لمحة عن جغرافية المجتمع الاباضي المغاربي الوسيط، خلال مخطوط كتاب السير لابي الربيع سلبمان الوسياني (القرن السادس هـ/12م) - قوجة, محمد (الحياة الثقافية, 2013)
Keywords: Prosopographie -- Afrique du Nord

Djerba se rêve au vert - Auffray, Elodie (Tour Hebdo, 2013)
Érosion des côtes, gestion de l’eau et des déchets… L’île est en proie à d’épineux problèmes d’environnement. Les autorités et quelques professionnels du tourisme tentent d’aller de l’avant
Keywords: Tourisme -- Djerba

دعوتي للجميع في هذا الوطن الغالي أن يحرصوا جميعا على مصلحه وبناته وازدهاره - البكوش, عادل (الصحوة, 2013)

The road to Djerba (The Economist, 2013)

Shakhṣiyya min al-Māḍī… Aw iḍāfat ḥawl al-shaykh Saʿīd b. ʿAlī b. Yaḥyā al-Khayrī al-Jarbī al-shahīr bi’l-Shaykh ʿAmmī Saʿīd al-ghardāwī (t. 927 h./1521 m.) - الباروني, سعيد بن يوسف (al-Jazira, 2013)
Keywords: Biographies -- Djerba

ديوان غار امجماج بجربة والعلاماء السبعة الذين الفوه - الباروني, سعيد بن يوسف (الحياة الثقافية, 2013)
Keywords: Fiqh -- Djerba; Fiqh -- Traité -- 11e siècle

الحومة بجزيرة جربة خلال العهد الوسيط: مفهومها، تاريخ ظهورها ومكوّناتها - بربو, المنصف (الحياة الثقافيّة, 2013)
Keywords: Urbanisme -- Djerba

Tunisie : le “nouveau Hitler” terrorise les juifs tunisiens à Djerba - Smith, Stephen (Jeune Afrique, 2013)
Keywords: Judaïsme -- Djerba

Le journal al-Jazira au creux de la vague : un patrimoine à sauvegarder au nom de la liberté d’expression - Bouabid, Naceur (al-Jazira, 2013)
Keywords: Journalisme -- Djerba

La gestion des déchets : où va la tunisie, … et notre pauvre île ? - Bouabid, Naceur (al-Jazira, 2013)
Keywords: Crises environnementales -- Djerba

Influences Ibadhites de Djerba - Maamer, Kérim (al-Jazira, 2013)
Keywords: Ibadisme -- Djerba

L’alerte est au rouge : La flèche de Ras R’mal à Djerba : une zone côtière vulnérable en péril - Bouabid, Naceur (al-Jazira, 2013)

Jerba et ses riches patrimoniales, leur inscription sur la liste du Patrimoine Mondial de l’humanité, s’impose - Tmarzizet, Kamel (al-Jazira, 2013)
Keywords: Monuments -- conservation -- Djerba

L’agroécologiste Pierre Rabhi en Tunisie,… Pour rédécouvrir le patrimoine oasien à Chénini Gabès et prendre connaissance du potentiel agricole à Djerba - Bouabid, Naceur (al-Jazira, 2013)
Keywords: Agriculture -- Djerba

A Jerba où l’eau manque, où la pollution est devenue un fléau d’effets nuisibles, la seule devise est « le gain et après nous le déluge ! » - Tmarzizet, Kamel (al-Jazira, 2013)
Keywords: Crises environnementales -- Djerba

Les Amazighen, Une ethnie dite berbère, d’art et de culture d’un passé lointain affirmé - Tmarzizet, Kamel (al-Jazira, 2013)
Keywords: Berbérisme -- Djerba

Tribune : Le patrimoine tunisien au péril du sectarisme - Barblan, Marc-Antonio (Kapitalis, 2013)
L'auteur, historien et muséologue, analyse la problématique du patrimoine en Tunisie, en réaction à la candidature de l'île de Djerba pour faire partie de la liste du Patrimoine Mondial de l'Unesco.
Keywords: Monuments -- conservation -- Djerba

«جربة» التونسية.. أساطير أهل الجزيرة - الرايس, حياة (Alrai, 2013)
«جربة» التونسية.. أساطير أهل الجزيرة
Keywords: Réformisme -- Djerba

Quelques tribus finirent par trouver refuge dans le kharégisme, secte religieuse révolutionnaire qui refuse tout compromis - Durand, Michel (En manque d'Eglise, 2013)
Keywords: Révoltes -- Afrique du Nord

Ibadisme et conflit (Islam) - Gil (Le conflit, 2013)
L'ibadisme, troisième branche de l'Islam, après le sunnisme et le chiisme, qui ne possède plus comme aire d'influence significative que l'Émirat d'Oman, est l'héritier (même si cet héritage est plutôt considéré aujourd'hui d'une manière négative) du khâridjisme...

Répartition des déchets de Djerba sur 5 zones provisoires - I.B. (Kapitalis, 2013)
Les déchets de la délégation de Houmet Essouk, chef-lieu de la délégation de Djerba, seront répartis sur 5 zones provisoires dans cette île à vocation touristique.
Keywords: Tourisme -- Djerba

Intellectual Network Map: 5th/11th Century | خريطة شبكة علمية: ق ٥/١١ - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2013)
Keywords: Prosopographie -- Afrique du Nord

Network Map: Trial Run! - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2013)
Keywords: Prosopographie -- Afrique du Nord

Geo-Distribution of Ibadi Scholars: Charts Posted - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2013)
Keywords: Prosopographie -- Afrique du Nord

Geographic Distribution of Ibāḍī scholars - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2013)
Keywords: Prosopographie -- Afrique du Nord

Mapping Ibāḍī Scholars across the Centuries: Experimental Stage 1 - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2013)
Keywords: Prosopographie -- Afrique du Nord

List of Ibāḍī Manuscripts at BNT in Tunis | قائمة المخطوطات الإباضية في المكتبة الوطنية التونسية - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2013)
Keywords: Manuscrits -- Tunis

Recent Conferences on Ibadism - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2013)

Ibadi MSS at the Bibliothèque Nationale de Tunisie - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2013)
Keywords: Manuscrits -- Tunis

Pèlerinage juif en terre d’Islam – La Hiloula de la Ghriba aura lieu du 13 au 18 mai 2014 - Bourial, Hatem (Webdo, 2013)
Keywords: Judaïsme -- Djerba

L’ibadisme à la base de la spécificité de l’identité des Jerbiens - Maamer, Kérim (la troisième république tunisienne, 2013)

Il faut sauver Djerba maintenant ! - Bourial, Hatem (Webdo, 2013)
Un petit pas en avant vient d’être fait à Djerba. Mais pour cela, il aura fallu l’explosion de colère d’octobre dernier, lorsque la population du paisible village de Gallala avait grondé pour faire entendre sa voix. On se souvient avec tristesse de ces deux journées d’émeute, de ces destructions et de toute la violence qui avait déferlé sur l’ile de Djerba. Quelques mois plus tard, les solutions pour la gestion des déchets, de plus en plus nombreux, commencent à trouver leur chemin et Djerba commence à panser ses plaies en matière d’environnement. Pourtant, le problème des déchets demeure entier et la pollution s’installe insidieusement dans les villes principales de Djerba mais aussi dans les campagnes les plus éloignées. Il est à ce titre désolant et à peine croyable de constater que dans le triangle rural Sidi Jmour – Bazim – Sidi Hachan, les décharges à ciel ouvert se sont multipliées, loin des regards, à cause de l’indiscipline des riverains et le laisser-aller général. A Djerba, il n y a pas que les déchets qui posent problème. L’équilibre écologique fragile de l’île subit les assauts du béton, du tourisme intensif et de l’urbanisation sauvage. En fait, l’île est quasiment défigurée et semble avoir perdu sa vocation de jardin miraculeux. Plusieurs actions associatives et aussi gouvernementales sont aujourd’hui entreprises mais que peuvent-elles face à la gabegie généralisée ? L’eau, rare et précieuse, est gaspillée sans vergogne, les menzels historiques sont remplacés par des buildings sans identité, les sentiers ruraux sont fragilisés par les quads et consorts qui s’infiltrent partout et, last but not least, ici aussi des zaouias ont été attaquées et détruites. Djerba souffre, c’est un fait. Pire, le seul site encore préservé de l’île commence à subir les assauts du béton. Tout le long de la plage qui mène jusqu’à Ajim, le rivage est carrément envahi par les déchets de toutes sortes. Ainsi, la seule plage dont les locaux font usage a pris une allure de dépotoir. On pourrait multiplier les exemples, établir une cartographie des dangers et demander des actions urgentes. Cela ne suffira pas et le projet d’île-jardin pour lequel le gouvernement promet de dépenser 16 millions d’euros tarde à voir le jour. Les menaces qui pèsent sur Djerba ne sont pas seulement écologiques. On constate ici et là des surenchères intégristes qui n’hésitent plus à s’exprimer haut et fort. Assistons-nous à un retour de l’intolérance dans ce havre béni des dieux ? En ce sens, cela constituerait un terrible recul. Pour l’heure, la nouvelle saison touristique sera certainement placée sous le signe de l’affluence libyenne et algérienne. Encore une fois, ce sont nos voisins qui vont sauver les meubles. Heureusement ! Encore faudrait-il, une fois pour toutes, réfléchir sur le destin futur de Djerba. Il est plus que temps : il faut sauver Djerba maintenant !
Keywords: Tourisme -- Djerba

Agressions contre des Juifs tunisiens à Djerba : Les valeurs de tolérance de l'île triompheront - Bouabid, Naceur (Turess, 2013)
Keywords: Judaïsme -- Djerba

Les élèves du lycée secondaire Houmt-Souk volent la vedette - Bouabid, Naceur (Turess, 2013)

Société civile et partis politiques à Djerba : Respect de l'autre et bannissement de l'exclusion - Bouabid, Naceur (Turess, 2013)

Djerba-Kerkennah : « Pour la reconnaissance des spécificités des îles tunisiennes » - Bouabid, Naceur (Turess, 2013)

Environnement L'alerte est au rouge : La flèche de Ras R'mal à Djerba: une zone côtière vulnérable en péril - Bouabid, Naceur (Turess, 2013)
Keywords: Crises environnementales -- Djerba

Une tortue «luth» dans les filets d'un pêcheur d'Adjim à Djerba - Bouabid, Naceur (Turess, 2013)
Keywords: Pêche -- Djerba

‏أعمال ندوة تطور العلوم الفقهية النظرية الفقهية والنظام الفقهي: ‏المنعقدة خلال عام 15-18 ‏جماد الأولى 1433هـ/7-10-4-2012م - ندوة تطور العلوم الفقهية (‏سلسلة الندوات, 2013)
Keywords: Fiqh

‏تاريخ المغرب الكبير - دبوز, محمد علي (عالم المعرفة, 2013)

اعلام الاصلاح في الجزائر من عام ١٣٤٠ه ، ١٩٢١م إلى عام ١٣٩٥ه، ١٩٧٥م - دبوز, محمد علي (عالم المعرفة, 2013)
Keywords: Réformisme -- Mzab

ملامح الحركة العلمية في وارجلان وضواحيها منذ انتهاء الدولة الرستمية حتى أواخر القرن السادس الهجري - النامي, عمرو خليفة (2013)
Keywords: Vie intellectuelle -- Ouargla

‏ذي قربتي - بابا عمي, محمد بن موسى (كتابك, 2013)

نفحات الرحمن في رياض القرآن - كعباش, محمد بن سعيد (جمعية النهضة, 2013)
Keywords: Coran -- Commentaires -- 2000-....

التأثير العثماني على الحياة الفنية و الثقافية في الجزائر - خالدى, محمد (جامعة قناة السويس - كلية الآداب والعلوم الإنسانية, 2013)
عرفت الثقافة في الجزائر خلال الفترة العثمانية تطورا داخل مؤسسات المسجد والمدرسة والزاوية والمكتبة، وأغلب هذه المؤسسات كان لغرض التعليم، وكانت مؤسسة الأوقاف ترعي وتمول هذه المؤسسات جميعا، ونتيجة لذلك عرفت الحياة العملية والأدبية شيئا من الازدهار، كما نشطت حركة التأليف. وعموما قد عرفت الحياة الثقافية خلال معظم فترات الوجود العثماني ركودا ملحوظا خاصة في فنون الأدب وعلم الأنساب والتاريخ. وإذا كان جميع الجزائريين الذكور قبل الاحتلال يحسنون القراءة والكتابة، إلا أن ذلك لم يخلف حركية علمية لمسايرة النهضة الأوروبية القائمة في الفكر والصناعة. وكان النشاط الفكري في مؤخرة اهتمامات الحكام الجزائريين في هذا العهد، فبغض النظر عن الجهود التي قام بها بعض البايات أمثال محمد الكبير أو صالح بأي، وهي فردية ونادرة وليست قائمة على سياسة مبرمجة ومستمرة. وأما اهتمام الجزائريين بالمسرح وفن التمثيل فيعود إلي زمن بعيد، حيث سجلت الكثير من الشهادات عن اهتمام الجزائريين بفن (خيال الظل) ذي الأصول التركية، ويؤكد الرحالة الألماني هاينريش فون مالتسان، إقبال الجزائريين في مدينة قسطنطينية علي مشاهدة حلقة من حلقات خيال الظل وهم عليه من الفقر، في مقهي متواضع، لكن ذلك لم يثنهم عن التعلق بهذا الفن، وكان (خيال الظل) منتشرا في أماكن أخرى من الجزائر. وفي لأخير يجب أن نشير إلي أهمية بعض المنشآت المكتبية المتفرقة في أنحاء البلاد، كمكتبات مزاب التي كانت مدينة بني يزجن تشتهر بها. والتي حافظ عليها أصحابها كعائلتي الثميني وأطفيش. كما كانت توات مركزا هاما لحركة الكتاب في غرب الجزائر وجنوبها، وكذلك كان الحال في مكتبات زواوة وبجاية وورقلة وغيرها، ووفرة الكتب في الجزائر حتى في المناطق النائية فيها يدل دلالة واضحة علي أن الإنسان الذي حافظ علي كل ذلك القدر من المكتبات كان علي درجة كبيرة من التحضر خلافا لزعم الفرنسيين عند احتلالهم للجزائر.

Ghardaia la mystérieuse - Bafouloulou, Salah (Imprimerie des Oasis, 2013)

الجيلاني بن الحاج يحيى يقظة فكرية وصدق وجدان - إبراهيم, عبد الواحد (ملتقى الجيلاني بالحاج يحيى لأعلام جربة (الدورة الأولى), 2013)
Keywords: Biographies -- Djerba -- 20e siècle

الجيلاني بن الحاج يحيى نظال ثقافي متنوع - بن مهني, الصادق (ملتقى الجيلاني بالحاج يحيى لأعلام جربة (الدورة الأولى), 2013)
Keywords: Biographies -- Djerba -- 20e siècle

الجيلاني بن الحاج يحيى بصمة أب وأثر صديق - بن الحاج يحيى, فتحي (ملتقى الجيلاني بالحاج يحيى لأعلام جربة (الدورة الأولى), 2013)
Keywords: Biographies -- Djerba -- 20e siècle

Séminaire Jilani Bel Haj Yahia - personnalités Djerbiennes (1ère édition) = ملتقى الجيلاني بالحاج يحيى لأعلام جربة (الدورة الأولى) (Association pour la Sauvegarde de l’île de Djerba, 2013)

إرشاد النساء إلى أحكام الدماء: الحيض - الإستحاضة - النفاس - الاجهاض - البوصافي, راشد بن سالم (مكتبة خزائن الآثار, 2013)

السلاسل الذهبية بالشمائل الطفيشية للشيخ العلامة الفقيه إبراهيم بن بكير حفار القراري - بن يوسف, عبد الرحمان بن عمر (مكتبة القطب, 2013)
Keywords: Vie religieuse -- Mzab

الشيخ إبراهيم أطفيش‏: ‏في جهاده الإسلامي - ناصر, محمد صالح (كولوريوم, 2013)
Keywords: Aṭfiyyash, Ibrāhīm b. Muḥammad (1886-1965); Biographies

Les Jerbiens et Kerkenniens à Tunis, ébauche d'une étude comparative - Ben Hamida, Abdessalem (Les migrations des Jerbiens et autres insulaires méditerranéens à travers les siècles, 2013)
Keywords: Emigration -- Djerba -- Tunis

Les insulaires djerbiens et kerkenniens à la Goulette - Kassar, Hassen (Les migrations des Jerbiens et autres insulaires méditerranéens à travers les siècles, 2013)
Keywords: Emigration -- Djerba -- Tunis

Les Jraba entre Nabeul et Djerba - El Ghoul, Yahya (Les migrations des Jerbiens et autres insulaires méditerranéens à travers les siècles, 2013)
Keywords: Emigration -- Djerba -- Tunis

Journalistes tunisiens originaires de Djerba pendant la période coloniale - Snoussi, Mohamed Larbi (Les migrations des Jerbiens et autres insulaires méditerranéens à travers les siècles, 2013)
Keywords: Journalisme -- Djerba

الإختصاصات الإقتصادية التي مارسها الشتات الجربي في مدينة تونس خلال الفترة الحديثة : بين الإحتكارات الإثنية والديناميكية الحرفية - الطبجي, إيناس (جربة ومحيطها البحري والقاري: ‏بحوث في التاريخ والجغرافيا والحضارة, 2013)
Keywords: Emigration -- Djerba -- Tunis

الجالية المالطية بجربة من خلال أوائل القرن 19 إلى أواسط القرن العشرين - بربو, المنصف (Les migrations des Jerbiens et autres insulaires méditerranéens à travers les siècles, 2013)
Keywords: Emigration -- Malte -- Djerba

الجرابة في الجزائر في القرن العشرين ومساهمتهم في المقاومة الجزائرية - الخروبي, حسين (Les migrations des Jerbiens et autres insulaires méditerranéens à travers les siècles, 2013)
Keywords: Emigration -- Djerba -- Algérie -- 20e siècle

الحضور الجربي في الحوض الشرقي للمتوسط من خلال مراسلات وكلاء الباي خلال القرن التاسع عشر - دالي, حمادي (Les migrations des Jerbiens et autres insulaires méditerranéens à travers les siècles, 2013)

تطور نشاط القرصنة بالحوض الأوسط للبحر المتوسط بين القرنين الحادي عشر والخامس عشر ميلادي - بن غازي, البشير (Les migrations des Jerbiens et autres insulaires méditerranéens à travers les siècles, 2013)

Le commerce des jarres jerbiennes en Sicile - Ardizzone, Fabiola (Les migrations des Jerbiens et autres insulaires méditerranéens à travers les siècles, 2013)
Keywords: Commerce -- Djerba

L'équilibre par l'absence : un modèle d'adaptation aux contraintes du milieu, le cas de Djerba - Bourgou, Mongi (Les migrations des Jerbiens et autres insulaires méditerranéens à travers les siècles, 2013)

Elites et richesses de Djerba à l'époque antique - Ben Omrane, Sadok (Les migrations des Jerbiens et autres insulaires méditerranéens à travers les siècles, 2013)
Keywords: Antiquité

Bir Deniz Savaşımızın Manzum Hikayesi: Fetihnâme-i Kal’a-i Cerbe - Ay, Ümran (2. Turgut Reis ve Türk Denizcilik Tarihi Uluslararası Sempozyumu, 2013)

Le référent ethnique dans les discours de fondation de l'ibadisme au Maghreb médiéval - Aillet, Cyrille (La fabrique de l’ethnie dans l’Islam médiéval, 2013)
Keywords: Ibadisme -- Afrique du Nord

La contribution des sources ibadites récemment éditées au "Sahara libyen" de Jacques Thiry - Prevost, Virginie (IVe journée d'études sur la Libye antique et médiévale, 2013)

A long, Centuries-Old Murmuring: Medieval Islamic Manuscripts and their modern Material Histories - Love Jr, Paul M. (The 19th Annual Charles F. Fraker Conference: Thinking with Things: Towards a Matter-Oriented Cultural Analysis, 2013)
Keywords: Manuscrits -- Djerba

فهرس كتاب بيان الشرع (الأجزاء 37-72) - الكندي, محمد بن إبراهيم (وزارة التراث القومي والثقافة, 2013)
Keywords: Catalogue -- Oman

فهرس كتاب بيان الشرع (الأجزاء 1-36) - الكندي, محمد بن إبراهيم (وزارة التراث القومي والثقافة, 2013)
Keywords: Catalogue -- Oman

‏الدين لله... والإباضية لا ينتظرون اعتمادا من الشيخ فركوس (الفجر, 2013)

الحاضر المغيب د. عمرو خليفة النامي (1939--؟؟؟؟؟) (جمعية الدعوة الإسلامية, 2013)
Keywords: Ennami, Amr (1939-198X)

يا غائبا وعيون الناس ترمقه الشهيد المغيب - النامي, عمرو خليفة; البغدادي, عبد المولى (المواطنة, 2013)

شهادة الدكتور علي مسعود المقدمي - المقدمي, علي مسعود (المواطنة, 2013)

غيابك طال - النامي, زينب عمرو (المواطنة, 2013)

الدكتور النامي من مدرجات جامعة كامبردج إلى رعي - الناكوع, محمود (المواطنة, 2013)

كلمة وفاء - أبو زعكوك, علي رمضان (المواطنة, 2013)

Introduction [Ibadism in Islamic medieval societies: Political models, social forms of organization and interaction] - Aillet, Cyrille (Ibadism in Islamic medieval societies:Political models, social forms of organization and interaction, 2013)

Conclusions and perspectives - Fierro, Maribel (Ibadism in Islamic medieval societies:Political models, social forms of organization and interaction, 2013)

La communauté ibadite entre l'Orient et l'Occident musulmans (IIIe/IXe-VIIe/XIIIe siècles) : trame d'une histoire d'échanges et construction identitaire - Dridi, Moez (Ibadism in Islamic medieval societies:Political models, social forms of organization and interaction, 2013)

L’ibadisme et la malikisation du Maghreb central : étude d’un processus long et complexe (IVe-VIe/Xe-XIIe siècles) - Amara, Allaoua (Ibadism in Islamic medieval societies:Political models, social forms of organization and interaction, 2013)

Le pouvoir almohado-hafside et les Ibadites en Ifriqiya - Hassen, Mohamed (Ibadism in Islamic medieval societies:Political models, social forms of organization and interaction, 2013)
Keywords: Djerba -- Hafsides

Fatimid Conflict with the Ibadis and the Ibadi Version of the Imamate, in North Africa and in the East - Walker, Paul E. (Ibadism in Islamic medieval societies:Political models, social forms of organization and interaction, 2013)

An Ibadi Islandscape: Djerba in the Medieval Centuries - Love Jr, Paul M. (Ibadism in Islamic medieval societies:Political models, social forms of organization and interaction, 2013)

Les paysages de l’eau sont-ils à l’image des sociétés qui les produisent ? Les oasis ibadites de l’Algérie méridionale, de l’oued Mya à l’oued Mzab - Cressier, Patrice; Gilotte, Sophie (Ibadism in Islamic medieval societies:Political models, social forms of organization and interaction, 2013)
Keywords: Archéologie -- Mzab

Analyse comparative de l'organisation urbaine des qṣūr du Sud-Est algérien (Rīgh, Miya, Mzab et al-Manīʻa) - Chekhab-Abudaya, Mounia (Ibadism in Islamic medieval societies:Political models, social forms of organization and interaction, 2013)
Keywords: Urbanisme -- Mzab

Le bassin de Ouargla, un carrefour aux marges du Maghreb médiévale - Aillet, Cyrille (Ibadism in Islamic medieval societies:Political models, social forms of organization and interaction, 2013)
Keywords: Archéologie -- Ouargla

Les communautés ibadites du nord du Sahara au Moyen Âge : espace et société dans la région du Wādī Rīgh - Meouak, Mohamed (Ibadism in Islamic medieval societies:Political models, social forms of organization and interaction, 2013)

Conclusions and perspectives - Brett, Michael (Ibadism in Islamic medieval societies:Political models, social forms of organization and interaction, 2013)

Le rôle des ʻazzāba dans l’organisation et la gestion des lieux de culte (mosquées, mosquées funéraires et madrasas) au Mzab - Maʿrūf, Bālḥājj (Ibadism in Islamic medieval societies:Political models, social forms of organization and interaction, 2013)
Keywords: Droit coutumier -- Mzab

La ḥalqa des ʻazzāba : pouvoir, société et organisation religieuse au sein de l'ibadisme maghrébin (IVe/Xe-VIe/XIIe siècles) - Bouchiba, Farid (Ibadism in Islamic medieval societies:Political models, social forms of organization and interaction, 2013)
Keywords: Idées politiques -- Ibadisme

Essai de cartographie des groupes schismatiques dans le Maghreb ibadite (IXe-XIIe siècles) - Prevost, Virginie (Ibadism in Islamic medieval societies:Political models, social forms of organization and interaction, 2013)

Ibadisme berbère ou Berbères ibadites ? - De Felipe, Helena (Ibadism in Islamic medieval societies:Political models, social forms of organization and interaction, 2013)

L’évolution de l'ibadisme dans le Djebel Nafūsa du VIIIe au IXe siècle - Mezhoudi, Messaoud (Ibadism in Islamic medieval societies:Political models, social forms of organization and interaction, 2013)

The political organization of Oman from the Second Imamate period to the Yaʻrūba: rereading Omani internal sources - Salimi, Abdulrahman al- (Ibadism in Islamic medieval societies:Political models, social forms of organization and interaction, 2013)

Premier bilan archéologique sur la Sijilmasa midraride - Fili, Abdallah (Ibadism in Islamic medieval societies:Political models, social forms of organization and interaction, 2013)
Keywords: Archéologie -- Sidjilmassa

Considérations sur la nature du pouvoir chez les Rustumides - Baḥḥāz, Ibrāhīm (Ibadism in Islamic medieval societies:Political models, social forms of organization and interaction, 2013)
Keywords: Dynastie rustumide

Conclusion and perspectives - Donner, Fred M. (Ibadism in Islamic medieval societies:Political models, social forms of organization and interaction, 2013)

Law and Policies in the Early Ibadi Communities: Abū ‘Ubayda al-Tamīmī’s Risālat to Abū ’l-Khaṭṭāb al-Ma’āfirī - Francesca, Ersilia (Ibadism in Islamic medieval societies:Political models, social forms of organization and interaction, 2013)
Keywords: Fiqh

Le kharijisme ibadite au Yémen et dans le Hadramawt à travers la révolte d’Ibn Yaḥya al-Kindī à la fin de l’époque omeyyade - Daghfous, Radhi (Ibadism in Islamic medieval societies:Political models, social forms of organization and interaction, 2013)
Keywords: Ibadisme -- Yemen

Les Ibâdites du Hadramawt : quelques suggestions généalogiques et historiographiques - Frantsouzoff, Serge A. (Ibadism in Islamic medieval societies:Political models, social forms of organization and interaction, 2013)

The early Ibāḍiyya and the Zaydiyya - Madelung, Wilferd (Ibadism in Islamic medieval societies:Political models, social forms of organization and interaction, 2013)

The Rebellion of Aṣfar at-Taghlibī (395/1004-5 to 406/1016) in Northern Mesopotamia: Social base-History-Religious and Political Goals - Heidemann, Stefan (Ibadism in Islamic medieval societies:Political models, social forms of organization and interaction, 2013)

The World Thus Became Severed from them: Khariji and Ibadi concepts of Shira’ in their Near Eastern Context - Gaiser, Adam R. (Ibadism in Islamic medieval societies:Political models, social forms of organization and interaction, 2013)
Keywords: Kharijisme

La SONEDE oublie Sakher El Materi (Maghreb confidentiel, 2013)
Keywords: Développement local -- Djerba

Et ainsi priait le prophète Mohammad - Ben Maad, Mongi (Les Editions Reconnaissance, 2013)
Presque toutes les différences entre les Ibadites, Malikites, Hanafites, Chafi’ites, Hanbalites ont leur origine dans les différentes pratiques du Prophète lui-même, qui n’a pas donné une importance particulière à telle ou telle forme. Comme le souligne l’auteur de l’ouvrage, le Prophète nous a transmis avec sa prière des valeurs spirituelles (recueillement, sérénité), morales (sincérité, piété), et sociales (humilité, fraternité, égalité) qui déterminent à la fois notre relation avec Dieu et avec les hommes.
Keywords: Fiqh -- prières

فقه التعايش عند الشيخ اطفيش من خلال كتابه "شرح النيل" - باجو, مصطفى بن صالح (أعمال ندوة تطور العلوم الفقهية: فقه رؤية العالم والعيش المشترك - المذاهب الفقهية والتجارب المعاصرة, 2013)
Keywords: Atfiyyash, Muhammad b. Yusuf (1821-1914)

الجالية الهندية و الإمامة الاباضية في عمان : دراسة في العلاقات المتبادلة بينهما في نماذج من التاريخ العماني بين عامي 1868 - 1920 - الفياض, مقدام عبد الحسن باقر (الخليج العربي, 2013)
حظيت الجالية الهندية في عُمان بمكانة متميزة لا تضاهى من بين مثيلاتها الجاليات الأجنبية الأخرى كالفارسية والأفريقية وغيرها، وذلك باستنادها الى العلاقات التاريخية والحضارية الوطيدة التي ربطت بين عمان وشبه القارة الهندية لعدة قرون مضت. أما الإمامة الاباضية فإنها بلا شك تعد معلماً أساسيا من معالم تاريخ عمان البعيد والقريب، وواحدة من القوى المهمة التي حركت الاحداث والتطورات وتحكمت بالأفراد والجماعات والعواطف والتوجهات في حياة معظم العمانيين. وتتجلى أهمية الموضوع في المحاولة لدراسة طبيعة العلاقات بين هاتين القوتين الهامتين اللتين تتربع إحداهما على قمة الهرم الديني أو الروحي والأخرى تحتل مكانة رفيعة في سلّم الاقتصاد والتجارة. \ وقد قُسّمت الدراسة الى عدد من المحاور، تناول الأول الجذور التاريخية لوجود الجالية الهندية في عمان وتطور دورها الاقتصادي، ودرس الثاني ماهية علاقتهم مع بريطانيا وتأثير حمايتها لهم على ترسيخ نفوذهم وتغير نظرة الناس إليهم. فيما ركز الثالث والرابع على مفهوم الإمامة وأهميتها التاريخ العماني، وحكمها بين عامي 1868-1871 وموقفها تجاه الجالية الهندية, وتخصص الخامس بكشف حقيقة الموقف بين الجالية الهندية وانتفاضة القبائل عام 1895، أما السادس فقد جاء ليلقي الضوء على تأثيرات ثورة الامامة 1913 على الجالية الهندية. \ واستعان الباحث بمصادر ومراجع متنوعة أتت في مقدمتها الكتب الوثائقية الأجنبية وأهمها ومجموعات سالدانا J.A. Saldanha وبيلي r.w. baily مجموعة عمان (الوثائق السرية). \ وعدداً من الرسائل و الاطاريح الجامعية العربية والانكليزية. واستفاد أيضاً من الكتابات المحلية وقائمة من البحوث والكتب المعربة والعربية والإنكليزية \
Keywords: Relations -- Oman -- Inde

Meouak Mohamed (éd.): Biografías magrebíes. Identidades y grupos religiosos, sociales y políticos en el Magreb medieval. - Buresi, Pascal (Bulletin critique des Annales islamologiques, 2013)
Keywords: Recension

قيام و تطور الدولة الرستمية في المغرب - عزب, محمد زينهم محمد (دار العالم العربي, 2013)
Keywords: Dynastie rustumide

Righteous Rebellion and Unjust Governance during the Reign of ‘Uthmān ibn ‘Affān (d. 656): A Reassessment of the Risālah of ‘Abd Allāh ibn Ibāḍ - Ballan, Mohamed (28th Annual Middle East History and Theory Conference, 2013)

المرحلة العمانية في حياة الشيخ سليمان الباروني (1924-1940م) - عباس, علي حمزة (مجلة أبحاث كلية التربية الأساسية, 2013)
Keywords: Bārūnī, Sulaymān al- (1870-1940)

The Forgotten Generation of Muscat: Reconstructing Omani National Identity After the Zanzibar Revolution of 1964 - Patterson, Molly (The Middle Ground Journal, 2013)

Guide to collections relating to Oman (St Antony’s College, 2013)
Keywords: Inventaire -- Oxford

مجموع البيان لحسن مكارم الأخلاق على مر الزمان - الغافري, مبارك بن سعيد (وزارة التراث والثقافة, 2013)

La Libye en fragments - Ammour, Laurence Aïda (Annuaire Français de Relations Internationales, 2013)
La nouvelle Libye est confrontée à une dégradation croissante de sa sécuritaire intérieure. Les tiraillements entre partisans de la centralisation et ceux du fédéralisme, entre groupes militarisés rivaux, entre communautés et tribus ou entre milices
Keywords: Vie politique -- Djebel Nefousa

أبو العباس أحمد بن سعيد الشماخي وآراؤه الأصولية - مصباح, عيسى بن باحمد (جامعة الجزائر, 2013)
Keywords: Foi -- Traité

A Grammar of Awjila Berber (Libya) based on Umberto Paradisi’s Material - Van Putten, Marijn (Leiden University, 2013)
Keywords: Linguistique -- Djebel Nefousa

Le militant libyen Madghis Umadi arrêté aujourd’hui à Tizi-Ouzou - Serrah, Madjid (Le Matin d'Algérie, 2013)

ندوة علمية موسعة لالحتفال بمرور 73 عاما على رحيل العلامة الليبي سليمان الباروني - الكندي, أحمد (الرؤية, 2013)
Keywords: Bārūnī, Sulaymān al- (1870-1940)

Zanzibar: Re-Searching the “Other Andalus” - Ghazal, Amal N. (al-Akhbar, 2013)
Keywords: Zanzibar

المنهل الصافي على فاتح العروض والقوافي - السالمي, عبد الله بن حميد (وزارة التراث والثقافة, 2013)

التعليم في سلطنة عمان 1970-1995 - عمر, باسمة عبد العزيز (مجلة كلية التربية الأساسية, 2013)
Keywords: Enseignement -- Oman

العلاقات العمانية الفرنسية في عهد السید سعید بن سلطان 1806م-1856م - عمر, باسمة عبد العزيز (مجلة التربیة والعلم, 2013)
When Sayyid Said Bin Sultan started leading Oman in 1806, the Omani-French relations were excellent and very prospective. The basis of such relation were trading with Meuritius island. Sayyid Said tried to continue such mode of relations taking into account keeping Oman away from the continuing French- Britain conflict those days. From its side, France worked on developing its relations with Muscat through some agreements, but the British occupation of Meuritius island in 1810 and French defeat destroyed the Omani-French relations. Five years after that, Britain retuned Meuritius to France in 1815. This led to rebuild the relations once again between Muscat and France via some trading and diplomatic agreements. This could not prevent the occur of some other conflicts in those relations because of the contradictions in occupation of some places and properties in East of Africa. Thus, these relations were highly affected by the abstract roll of Britain. This forced Sayyid Said to establish some consulting agreement with Britain to supervise his relations with France in older to keep France away his properties. He always took the right decisions to get much benefits with less losses.
Keywords: Relations -- Oman -- France

شروط الإمامة عند الرستميين - بحاز, إبراهيم بن بكير (مجلة الواحات للبحوث والدراسات, 2013)
Keywords: Dynastie rustumide

التنمية والتحضر في الجبل الأخضر: سلطنة عمان - المختار, بالقاسم بن محمد (رؤى استراتيجية, 2013)

Prophetic Traditions about the Virtues of the Berbers in the North African Ibadi Tradition - Ballandalus (Ballandalus, 2013)
The following is excerpted from Ibn Sallām, Kitāb fīhi bada’ al-islām wa sharā’i‘ al-dīn, pp. 121–125. This book, written by an Ibadi from the Tripolitania region, is the first-known historical acc…

The Sultanate of Oman: Sons and Daughters - Arslanian, Artin H. (Digest of Middle East Studies, 2013)
Keywords: Vie politique -- Oman -- 1970-2020

من فقه الأحاديث الواردة في الخوارج - أبو سعيد بلعيد بن أحمد (الخوارج وبقاؤهم إلى زمن الدجال, 2013)

Choses vues et entendues à Ghardaïa: éloge du vivre-ensemble - Chitour, Chems Eddine (L'Expressiondz, 2013)
Keywords: Vie culturelle -- Mzab

Tunus Üzerinde Osmanli-Ispanyol Hâkimiyet Mücadelesi (xvi. Asir) - Bilgin, Feridun (Elektronik Sosyal Bilimler Dergisi, 2013)
The sixteenth century is the time when two great states representing two great civilizations (Islamic and Western) reached their apex on the historical scene. In this century the Ottoman state saw itself as the most powerful state and protector of the Islamic world whereas Catholic Spain regarded itself as the defender of the West and of Christianity. Impelled by religious, military and economic motives these two states confronted each other in order to obtain the overlordship of the geopolitically crucial region of Tunisia in the Central Mediterranean. In the sixteenth century Tunisia gained importance for the Ottomans as a place that needed to be conquered for two reasons: it was situated at the connecting point with Algeria, which was their most important province in Northern Africa; and it was found in a place that controlled the trade routes in the Mediterranean. By contrast, the Spanish state considered it to be of vital importance for the protection of its garrisons in Northern Africa and for the security of its lands in Southern Italy.

العلاقات العمانية-الهندية حتى عام 1556 - العويدي, فؤاد طارق كاظن (جملة القادسية للعلوم اإلنسانية, 2013)

‘The Land of Security’: Western Perceptions of Religious Tolerance in Oman - Hajri, Hilal al- (British Journal of Arts and Social Sciences, 2013)
Oman in 1970, with the advent of Sultan Qaboos bin Said to power, became a modern country. The Sultan worked on the establishment of a civil state based on the foundations of citizenship, equality and social justice. Education, health, human services and government positions, are available to all Omanies, regardless of their origins and sects. He also ordered the issuance of a cultural journal entitled Al-Tasamoh (tolerance), which began publication in 2003. Its main objective was to promote understanding and brotherhood among international societies. Religious tolerance, as we shall see in this paper, is deeply rooted in the Omani culture. This paper explores Western perceptions of religious tolerance in Oman. In the writings of Western travellers and missionaries, the theme of 'tolerance' will be traced.
Keywords: Tolérance religieuse -- Oman

British Travel Writing on Oman : Orientalism Reappraised = عمان في عيون الرحالة البريطانيين: قراءه جديدة للاستشراق - الحجري, هلال بن سعيد (النادي الثقافي, 2013)
Keywords: Récits de voyage -- Oman

Theologies of Violence: The Recruitment of Muslim Soldiers by The Crown of Aragon - Fancy, Hussein (Past & Present, 2013)
Keywords: Invasions chrétiennes -- Djerba

Q&A about Ibadism and Prayer - Miwali, Hamad Bin Suleiman al- (Jabir bin Zayd Library, 2013)
Keywords: Fiqh -- prières

The history of Oman in Brazil - Aurea, Santos (Agência de Notícias Brasil-Árabe, 2013)
Keywords: Relations -- Oman -- Brésil

Talmudic Commentary in Djerba: Trumat Hadeshen by Rabbi Tzemach Cohen - Ahrend, Aaron (Sidra: A Journal for the Study of Rabbinic Literature / סידרא: כתב-עת לחקר ספרות התורה שבעל-פה, 2013)
"Talmuic Commentary in Djerba: Trumat Hadeshen by Rabbi Tzemach Cohen", Sidra, 27-28 (2013), pp. 7-25 (Hebrew)
Keywords: Judaïsme -- Djerba

Financement et lobby: l'impact des berbères libyens sur la chute de Khadafi (2) - Moreau, Aurélie (2013)
Financement occulte, stratégie médiatique, lobbying: dans la seconde partie de cette enquête, nous observons comment la communauté berbère a influencé de manière déterminante le déroulement de la…
Keywords: Berbérisme -- Libye

Six ans avant, comment les berbères libyens préparaient la chute de Kadhafi (1) - Moreau, Aurélie (2013)
A l’étranger ou en Libye, les Berbères ont contribué à la victoire des forces révolutionnaires face à Kadhafi, durant la guerre civile libyenne. Sur le terrain d'abord, où ils ont mené plusieurs…
Keywords: Berbérisme -- Djebel Nefousa

Etude sur les « Organisations et initiatives en faveur de la participation des jeunes dans la commune de Jerba Midoune » - Ben Abdallah, Sénim; Saadi, Lotfi (Comun, 2013)
Keywords: Communes -- Djerba

イバード派イスラーム思想における共同体論の研究 - Kondo, Yohei (The University of Tokyo, 2013)

The Rise of Tribal Politics - Pack, Jason; Larcher, Wolfram (The 2011 Libyan Uprisings and the Struggle for the Post-Qadhafi Future, 2013)
Keywords: Vie politique -- Djebel Nefousa

The end of the Pagan city: religion, economy, and urbanism in Late Antique North Africa - Leone, Anna (Oxford University Press, 2013)

The Solitary Sultan and the Construction of the New Oman - Peterson, John E. (Governance in the Middle East and North Africa: a handbook, 2013)
Keywords: Vie politique -- Oman -- 1970-2020

أبو اليقظان ودوره في الحركة الاصلاحية في الجزائر (1888-1973) - ربيعة, ناصر (جامعة محمد خيضر, 2013)
Keywords: Réformisme -- Mzab

حديث جابر بن سمرة في النهي عن رفع اليدين في الصلاة. دراسة نقدية تخصصية وفق مناهج المحدثين - السابعي, ناصر بن سليمان (دراسات وبحوث, 2013)
Keywords: Fiqh -- prières

Oman - Jawhari, Nasser Said al- (Bulletin of the British Foundation for the Study of Arabia (BFSA), 2013)
Archaeological Activities Conferences and Workshops

مسائل علم الكلام عند الإباضية عمرو خليفة النامي أنموذجا - نجار, أبو اليقظان; شعلان, ياسين (جامعة الأمير عبد القادر, 2013)

‏منهج الشيخ بيوض في الاجتهاد الفقهي - فخار, جابر بن سليمان (جامعة الجزائر, 2013)
Keywords: Bayyūḍ, Ibrāhīm ibn ʿUmar (1899-1981); Fiqh; Fiqh -- Mzab -- 20e siècle; Ijtihad -- Mzab -- 20e siècle

Planchers des constructions traditionnelles dans la vallée du M'zab - Baghbagha, Abdelaziz (ديوان حماية وادي الميزاب وترقيته - OPVM, 2013)
Keywords: Artisanat -- Mzab

‘They are the most treacherous of people’: religious difference in Arabic accounts of three early medieval Berber revolts - Clarke, Nicola (eHumanista, 2013)
Keywords: Révoltes -- Afrique du Nord

قراءة في فكر الدكتور النامي من خلال آثاره العلمية - تفوشيت, خالد سعيد (المواطنة, 2013)
Keywords: Ennami, Amr (1939-198X)

‏محمد بن عمر ابن أبي ستة المشهور بالمحشي حياته والآثاره - بن يحياتن, خالد ‏بن يوسف (‏معهد العلوم الشرعية, 2013)

Peut-on encore sauver la presse régionale ? (Leaders, 2013)
Keywords: Journalisme -- Djerba

L’habitat mozabite au M’Zab - Bousquet, Christian (Habitat, État, société au Maghreb, 2013)
Keywords: Urbanisme -- Mzab

The Bilād al-Maghrib: Rebels, Saints, and Heretics - Loimeier, Roman (Muslim societies in Africa: a historical anthropology, 2013)

Guide des sites et monuments historiques de la wilaya de Ghardaia - Lallout, Bahmed; Baghbagha, Abdelaziz; Zababe, Khoudir (ديوان حماية وادي الميزاب وترقيته - OPVM, 2013)
Keywords: Monuments -- conservation -- Mzab

‏النصوص القانونية المتعلقة بالتراث الثقافي الجزائري (ديوان حماية وادي الميزاب وترقيته - OPVM, 2013)
Keywords: Monuments -- conservation -- Mzab

Les stucs de Sedrata (Ouargla, Algérie). Perspectives d’étude - Cressier, Patrice; Gilotte, Sophie (Patronato de la Alhambra y Generalife, 2013)
Keywords: Archéologie -- Sedrata

منهاج المتعلمين - الرستاقي, راشد بن عميرة (وزارة التراث والثقافة, 2013)

Kashf al-Ghumma al-jāmiʿ li-Akhbār al-Umma - Izkawī, Sirḥān b. Saʿīd (Ministry of Heritage and Culture, 2013)

Kashf al-Ghumma al-jāmiʿ li-Akhbār al-Umma - Izkawī, Sirḥān b. Saʿīd (Ministry of Heritage and Culture, 2013)

Kashf al-Ghumma al-jāmiʿ li-Akhbār al-Umma - Izkawī, Sirḥān b. Saʿīd (Ministry of Heritage and Culture, 2013)

“Regionalizing Oman”: A New Interest of Research on Oman and Its Spatial Dimensions - Wippel, Steffen (Regionalizing Oman: Political, Economic and Social Dynamics, 2013)

النازع الإمراتي السعودي حول واحة البريمي والموقف البريطاني والأمريكي منها - الطفيمي, ستار عممك (مجلة كلية التربية الأساسية, 2013)
Keywords: Relations -- Oman -- Arabie Saoudite

Place and Role of Shura Council in Oman Law System - Busaidi, Y. Y. al- (2013)
The article examines radical changes both in the procedure of Shura Council formation and in its field of competence. The structure of the Council comes under review and the place and role of its main authorities in supporting the government on different running the state issues is determined. Considering and examining the many years' experience of the Council the author has come to the conclusion that the role of the Shura Council is limited only by the government in addressing certain issues. The Council studies these issues and provides recommendations to the Sultan for approval. These recommendations have no legal force, and the Council cannot impose its views on the Government. Despite this fact, the Council in its current form can become the basis for the future Parliament of Oman. To make this happen, in our opinion, it is necessary that the Council be directly involved in the discussion and approval of the state budget. It is also important to make the government accountable to the Council and to report to him about the results of its work.
Keywords: Vie politique -- Oman -- 1970-2020

Peculiarities of Oman Imamate Law System - Busaidi, Y. Y. al- (2013)
The article examines the evolution and peculiarities of the Imamate institute in Oman. Special attention is paid to the Ibadi movement of Islamic law as well as to the tribal common law both of which form the basis for the analysis of the role of Shura Council and influential circles for the purpose of gaining certain balance in relations between the authorities of the country and its inhabitants. Our analysis shows that until the middle of the XX century Oman was a union of tribes supporting Ibadi Islam. Within Ibadi doctrine for the first time in the history of Muslim societies the principles of people's participation in public administration were developed, which resulted in the outward expression in imamate moderate state system. Imam ruled the country with the help of the Council of theologians, the Shura Council, as well as governors and heads of tribes. For centuries Imamate and its institutions ensured the safety of society and order in social relations. Oman Imamate guaranteed gradual strengthening of the tradition of social relations and its steadiness. The effectiveness of such a form was confirmed by the fact that such statehood existed for twelve centuries.
Keywords: Vie politique -- Oman -- 1970-2020

إضاءات حول الدكتور عمرو خليفة النامي - أوشن, زهرة سليمان (المواطنة, 2013)

Slavery and Emancipation in Islamic East Africa - McMahon, Elisabeth (Cambridge University Press, 2013)
Keywords: Esclavage -- Zanzibar

Oman, entre forteresses et déserts, tradition et modernité - Apert, Sophie (2013)

L'invitation du M'zab: les impressions de Bennabi - Sifaoui, Abdelatif (Le Jeune Musulman, 2013)
Keywords: Récits de voyage -- Mzab

التحفة السنية على متن الآجرومية في علم العربية - الكندي, سليمان بن أحمد (وزارة الأوقاف والشؤون الدينية, 2013)

مدينة المدن تستقبل طلائع رواد المعرفة بنغازي تكرم عمرو النامي - قنيبر, سالم (المواطنة, 2013)
Keywords: Ennami, Amr (1939-198X)

بنغازي تكرم عمرو النامي - قنيبر, سالم (المواطنة, 2013)
Keywords: Ennami, Amr (1939-198X)

Développement et fragmentation d’une ville moyenne en cours de mondialisation : le cas de Salalah (Oman) - Wippel, Steffen (Arabian Humanities, 2013)
L’étude de la reconfiguration économique et spatiale actuelle de la ville de Salalah, dans le Sud du Sultanat d’Oman, invite à porter l’attention sur la problématique des « villes secondaires » arabes dans le Golfe, trop négligées ces dernières années au profit des grandes villes. Salalah n’est apparue sur la carte économique mondiale qu’après la construction de son port à conteneurs vers la fin des années 1990, port qui est en passe d’être complété par d’autres projets industriels, touristiques, infrastructurels et urbains majeurs. L’article tente de comprendre dans quelle mesure Salalah peut être conçue aujourd’hui comme une ville « en cours de mondialisation » et comment elle développe des qualités perçues comme caractéristiques des villes « postmodernes » et portuaires contemporaines. L’analyse porte enfin sur la fragmentation de l’actuelle agglomération urbaine, qui résulte de l’établissement de projets à accès limité et économiquement intégrés aux circuits mondiaux plus que locaux.
Keywords: Urbanisme -- Oman

Concluding Remarks: Regionalizing Oman Beyond Conventional Metageographies - Wippel, Steffen (Regionalizing Oman: Political, Economic and Social Dynamics, 2013)

Bringing the Global and the Local Together Through English in Oman - Mahrooqi, Rahma Ibrahim al-; Tuzlukova, Victoria (Regionalizing Oman: Political, Economic and Social Dynamics, 2013)

The Political Economy of Internationalization and Privatization of Higher Education in the Sultanate of Oman - Brandenburg, Torsten (Regionalizing Oman: Political, Economic and Social Dynamics, 2013)

Musandam: Creating a New Region Across the Water - Dietl, Gulshan (Regionalizing Oman: Political, Economic and Social Dynamics, 2013)

Domesticating Local Elites. Sheikhs, Walis and State-Building Under Sultan Qaboos - Valeri, Marc (Regionalizing Oman: Political, Economic and Social Dynamics, 2013)
Keywords: Vie politique -- Oman -- 1970-2020

Private Documents as a Source for Regional History: The Archive of the ʿAbrīyīn of Al-Ḥamrāʾ - Hoffmann-Ruf, Michaela (Regionalizing Oman: Political, Economic and Social Dynamics, 2013)
Keywords: Archives -- Oman

The Impact of Shopping Malls on Traditional Retail Stores in Muscat. Case Study of Al-Seeb Wilayat - Abdelghani, Montasser I.M. (Regionalizing Oman: Political, Economic and Social Dynamics, 2013)
Keywords: Tourisme -- Oman

Is Littoralization Reconfiguring the Omani Territory? - Mokhtar, Belgacem (Regionalizing Oman: Political, Economic and Social Dynamics, 2013)
Keywords: Littoraux -- Djerba

Musandam and Its Trade with Iran. Regional Linkages Across the Strait of Hormuz - Benz, Michael (Regionalizing Oman: Political, Economic and Social Dynamics, 2013)

Oman Caught Between the GCC Customs Union and Bilateral Free Trade with the US: Is It Worth Breaking the Rules? - Zorob, Anja (Regionalizing Oman: Political, Economic and Social Dynamics, 2013)

Oman and the Indian Ocean Rim – Economic Integration Across Conventional Meta-Regions - Wippel, Steffen (Regionalizing Oman: Political, Economic and Social Dynamics, 2013)

Re-reading the Role of Oman Within Its International Trade Relations: From the Sixteenth Through to the Nineteenth Centuries - Nicolini, Beatrice (Regionalizing Oman: Political, Economic and Social Dynamics, 2013)

Negotiating Authenticity and Translocality in Oman: The “Desertscapes” of the Harasiis Tribe - Chatty, Dawn (Regionalizing Oman: Political, Economic and Social Dynamics, 2013)

Oman-India Relations: Exploring the Long-Term Migration Dynamics - Pradhan, Samir (Regionalizing Oman: Political, Economic and Social Dynamics, 2013)

Of Red Cells, Translocality and Origins: Inherited Blood Disorders in Oman - Beaudevin, Claire (Regionalizing Oman: Political, Economic and Social Dynamics, 2013)
Keywords: Biologie -- Oman

“We Are Part of Zanzibar” – Translocal Practices and Imaginative Geographies in Contemporary Oman-Zanzibar Relations - Verne, Julia; Müller-Mahn, Detlef (Regionalizing Oman: Political, Economic and Social Dynamics, 2013)
Keywords: Relations -- Oman -- Afrique de l'Est

La militarisation du Sud de l’Empire : l’exemple du Fezzan libyen pendant la gestion coloniale de l’Italie et de la France de 1935 à 1951 - Palmieri, Tommaso (Institut de Recherches et d’Etudes sur le Monde Arabe et Musulman, 2013)

From Siraf to Sumatra: Seafaring and Spices in the Islamicate Indo-Pacific, Ninth-Eleventh Centuries C.E. - Averbuch, Brian (Harvard University, 2013)
Keywords: Zanzibar

الإيمان عند الإباضية - إكريبات, سدينة علي صالح (فكر وإبداع, 2013)

من مدن جبل نفوسة - حامد, سعيد علي (mirathlibya, 2013)

Les anciens et nouveaux ksour : étude comparative, cas du M'zab - Adad, Mohamed Cherif; Mazouz, Touffik (Courrier du savoir, 2013)
Keywords: Urbanisme -- Mzab

آراء الخوارج الكلامية: الموجز لأبي عمار عبد الكافي الأباضي - عبد الكافي, أبو عمّار (موفم للنشر, 2013)
Keywords: Foi -- Traité -- 12e siècle

ʻUmān wa-al-siyāsah al-Brīṭānīyah fī Sharq Ifrīqiyā: 1806 - 1862 M - ʿUjaylī, Ghānim Muḥammad Ramīḍ (al-Dār al-ʻArabīyah lil-Mawsūʻāt, 2013)
Keywords: Relations -- Oman -- Afrique de l'Est

Repurposed Narratives: The Battle of Ṣiffīn and the Historical Memory of the Umayyad Dynasty - Hagler, Aaron M. (Mathal, 2013)

Muscae moriturae donatistae circumvolant: la costruzione di identità "plurali" nel cristianesimo dell'Africa romana - Rossi, Alessandro (Dipartimento di studi storici, 2013)
Keywords: Donatisme

Heurts à Ghardaïa : "la précarité de la région attise les tensions" - Chegrouche, Lagha (2013)
Keywords: Conflits -- Mzab

Fihris Makhṭūṭāt Khizānat Mu'allafāt al-Shaykh al-ʿAllāma Amuḥammad b. Yūsuf Iṭfayyish al-Yasjanī al-Shahīr bi'l-Quṭb bi-Banī Yazqan - Syūsyū, Ṣāliḥ b. Bakīr; Būsnān, Muḥammad b. ʿUmar (Maktabat al-Quṭb, 2013)
Keywords: Bibliothèques -- Mzab; Catalogue -- Mzab; Manuscrits -- Mzab

L’espace habité en Oman (xviie - première moitié du xxe siècle) : modèles, fonctionnement et perceptions locales - Andriyanova, Olga (Hypothèses, 2013)
Keywords: Urbanisme -- Oman

Tārīkh al-siyāsī wa’l-ḥaḍārī li-Jazīrat Jarba mundh al-fatḥ al-islāmī ḥatā suqūṭ al-dawla al-ḥafṣiyya - Manshāwī, Muḥammad Maḥmūd (Jāmiʿat al-Fayyūm, 2013)

El Ghriba Synagogue in Djerba, Pilgrimage Site - Jarrassé, Dominique (A history of Jewish-Muslim relations: from the origins to the present day, 2013)
Keywords: Judaïsme -- Djerba

خصوصية ديناميكية المجتمع بجزيرة جربة ومقوماتها - المريمي, محمد (الحياة الثقافية, 2013)
Keywords: Djerba -- Empire ottoman; Ibadisme -- Djerba

‏متاحف الفنون والعادات الشعبية بجزيرة جربة: متحف جربة للتراث التقليدي الحوافر والحدود الأفق - ثابت, علي (Institut Supérieur des Sciences Culturelles et Métiers du Patrimoine, 2013)
Keywords: Musée -- Djerba

الميزان القسط - الحجري, علي (منشورات موقع بصيرة الالكتروني, 2013)

Jarba akhbār ʿan ʿāʾilāt al-khalfat al-wazdārī al-Zuwārī wa mā tafraʿ ʿanha min al-ʿāʾilāt al-muntamiyya ilā « mistāwā » Ḥumt al-Hanshīr bi’l-maḥbūbiyyīn bi-Jarba - Ibn Jumʿā, Nūr al-Dīn (Stag, 2013)

The Baluch presence in the Persian Gulf - Peterson, John E. (Sectarian Politics in the Persian Gulf, 2013)
Keywords: Vie politique -- Oman -- 1970-2020

Identity and Belonging among Ethnic Return Migrants of Oman - Kharusi, Nafla S. (Nationalism and Ethnic Politics, 2013)

Star charts of Oman - Nash, Harriet; Agius, Dionisius A. (Sources and approaches across disciplines in Near Eastern studies: proceedings of the 24th congress, Union Européenne des Arabisants et Islamisants, Leipzig 2008, 2013)
An overview of the Falaj systems and timing of water shares, followed by an explanation of the provenance of the only three documents related to the practice of star gazing found (all from the 20th century) and a discussion of their application and significance.
Keywords: Navigation -- Oman

Ghuṣn al-Bān fī Tārikh Warjlān - Aʿzām, Ibrāhīm b. Ṣālaḥ Bābā Ḥammū (Balghanim, 2013)
Keywords: Ouargla -- Histoire

القَصائد العمانية في الرحلة البارونية - الطائي, عيسى بن صالح (ذاكرة عمان, 2013)
Keywords: Bārūnī, Sulaymān al- (1870-1940)

Maṣādir Makt. al-Quṭb Iṭfayyish min khārij al-Jazā’ir - Syūsyū, Ṣāliḥ b. Bakīr (Al-Minhāj, 2013)
Keywords: Manuscrits -- Mzab

Nāfidha ʿalà Makhṭūṭāt al-Khizāna al-ʿĀmma li-Mu’assasat ʿAmmī Saʿīd bi-Ghardāya - Ḥājj Mūsà, Bashīr b. Mūsà al- (Al-Minhāj, 2013)
Keywords: Bibliothèques -- Mzab; Catalogue -- Mzab; Manuscrits -- Mzab

Mashrūʿ Jawābāt al-Imām al-Quṭb AMuḥammad b. Yūsuf Iṭfayyish - Ḥājj Mūsà, Bashīr b. Mūsà al- (Al-Minhāj, 2013)
Keywords: Atfiyyash, Muhammad b. Yusuf (1821-1914)

al-Mīzābiyya bi-Madīnat Tūnis fī ‘l-Qarnayni al-tāsiʿ ʿashar wa’l-ʿishrīn min khilāl Wathā’iq al-Arshīf - Mājirī, ʿAbd al-Karīm al- (Al-Minhāj, 2013)
Keywords: Emigration -- Mzab -- Tunisie

Namūdhaj min al-Buḥūth al-Istishrāqiyya: Mīzāb wa’l-Ibāḍiyya fī ‘l-Dirāsāt al-Būlūniyya - Ibn Idrīsū, Ṣāliḥ (Al-Minhāj, 2013)
Keywords: Lewicki, Tadeusz (1906-1992); Smogorzewski, Zygmunt (1884-1931)

al-Tawāṣul al-Maʿrifī li’l-Muʿāraḍa al-Ibāḍiyya fī ‘l-Mashriq wa’l-Maghrib - Ibn Idrīsū, Muṣtafà b. Muḥammad (Al-Minhāj, 2013)

al-Shaykh al-Ḥājj AMuḥammad b. Yūsuf Iṭfayyish wa’l-Istiʿmār al-Faransī - Ḥammūda, Muṣṭafà b. al-Ḥājj Bakīr (Al-Minhāj, 2013)
Keywords: Atfiyyash, Muhammad b. Yusuf (1821-1914)

Sijillāt Aḥkām Majlis ʿAmmī Saʿīd: Qirā’a Waṣfiyya Taḥlīliyya - Ḥadbūn, Muḥammad (Al-Minhāj, 2013)
Keywords: Droit coutumier -- Mzab

al-Ḥayāt al-Fikriyya bi-Manṭiqat Mzāb fī ‘l-Qarnayni 9-10 H./15-16 M. Makhṭūṭ Ajwibat al-Shaykhayni Saʿīd al-Jarbī wa-ʿĪsà al-Muṣʿabī Unmūdhajan - Būrās, Yaḥyà (Al-Minhāj, 2013)
Keywords: Vie intellectuelle -- Mzab

طلبة جربيون ونفوسيون لدى القطب اطفيش في نهاية القرن 19م من خلال وثائق أرشيفية فرنسية - ناصر, بالحاج بن باحمد (المنهاج, 2013)
Keywords: Atfiyyash, Muhammad b. Yusuf (1821-1914); Emigration -- Djebel Nefousa -- Mzab; Emigration -- Djerba -- Mzab

Multaqà al-Tawāṣul al-ʿUmānī al-Maghāribī: Sul. Bāshā al-Bārūnī wa-Ḥuḍūruhu fī ‘l-Thaqāfa al-ʿUmāniyya - Bābāwāsmāʿīl, Zuhayr b. Masʿūd (Al-Minhāj, 2013)
Keywords: Bārūnī, Sulaymān al- (1870-1940)

al-Minhāj (2013)
Keywords: Périodiques -- Mzab

The abolition of slavery in Ottoman Tunisia - Montana, Ismael Musah (Univ. Press of Florida, 2013)
The first full examination of the factors for and against abolition in Tunisia and how it was able to occur in an environment hostile to such change
Keywords: Esclavage -- Tunisie

La théorie de l’acte humain dans la pensée ibadite et ašˁarite - Ismāʿīlī, Aḥmad (Al-Andalus Magreb, 2013)

al-Istibdād: Maẓāhiruhu wa-Muwājahatuhu - Khalīlī, Aḥmad b. Ḥamad al- (Baseera, 2013)

Riḥlat Sulaymān Bāshā al-Bārūnī al-ʿIlmiyya ilà Maʿhad al-Quṭb wa-Atharuhā fī Takwīnihi ‘l-Fikrī wa’l-ʿIlmī - Wāsmāʿīl, Zuhayr (al-Nadwa al-Duwaliyya: Sulaymān Bāshā al-Bārūnī wa-Ḥuḍūruhu fī ‘l-Thaqāfa al-ʿUmāniyya, 10-11 Yūlyū 2012. Buḥūth al-Nadwa, 2013)
Keywords: Bārūnī, Sulaymān al- (1870-1940)

al-Bārūnī Mufakkiran wa-Muṣliḥan - Wā’ilī, Saʿīd b. Sulaymān al- (al-Nadwa al-Duwaliyya: Sulaymān Bāshā al-Bārūnī wa-Ḥuḍūruhu fī ‘l-Thaqāfa al-ʿUmāniyya, 10-11 Yūlyū 2012. Buḥūth al-Nadwa, 2013)
Keywords: Bārūnī, Sulaymān al- (1870-1940)

Sulaymān Bāshā al-Bārūnī: ʿAlāqatuhu bi-A’immat ʿUmān wa-Salāṭīnihā wa-Juhūduhu ‘l-Fikriyya wa’l-Iṣlāḥiyya - ʿUbaydī, Sālim b. Hāshil al- (al-Nadwa al-Duwaliyya: Sulaymān Bāshā al-Bārūnī wa-Ḥuḍūruhu fī ‘l-Thaqāfa al-ʿUmāniyya, 10-11 Yūlyū 2012. Buḥūth al-Nadwa, 2013)
Keywords: Bārūnī, Sulaymān al- (1870-1940)

al-Marḥala al-ʿUmāniyya fī Ḥayāt al-Bārūnī bi-Dākhiliyyat ʿUmān - Shuʿaylī, Muḥammad b. Sulaymān al- (al-Nadwa al-Duwaliyya: Sulaymān Bāshā al-Bārūnī wa-Ḥuḍūruhu fī ‘l-Thaqāfa al-ʿUmāniyya, 10-11 Yūlyū 2012. Buḥūth al-Nadwa, 2013)
Keywords: Bārūnī, Sulaymān al- (1870-1940)

al-Marḥala al-ʿUmāniyya fī Ḥayāt al-Shaykh Sulaymān al-Bārūnī (1924-1940) - Ṣawwāfī, ʿAlī Ḥamza al- (al-Nadwa al-Duwaliyya: Sulaymān Bāshā al-Bārūnī wa-Ḥuḍūruhu fī ‘l-Thaqāfa al-ʿUmāniyya, 10-11 Yūlyū 2012. Buḥūth al-Nadwa, 2013)
Keywords: Bārūnī, Sulaymān al- (1870-1940)

Ḥuḍūr Sulaymān al-Bārūnī fī ‘l-Ṣiḥāfa al-Iṣlāḥiyya al-Jazā’iriyya (1920-1940) - Qawbaʿ, ʿAbd al-Qādir (al-Nadwa al-Duwaliyya: Sulaymān Bāshā al-Bārūnī wa-Ḥuḍūruhu fī ‘l-Thaqāfa al-ʿUmāniyya, 10-11 Yūlyū 2012. Buḥūth al-Nadwa, 2013)
Keywords: Bārūnī, Sulaymān al- (1870-1940)

Riḥlāt al-Bārūnī wa-Ahdāfuhā - Nāʿibī, Sulṭān b. Khamīs b. ʿĪsà al- (al-Nadwa al-Duwaliyya: Sulaymān Bāshā al-Bārūnī wa-Ḥuḍūruhu fī ‘l-Thaqāfa al-ʿUmāniyya, 10-11 Yūlyū 2012. Buḥūth al-Nadwa, 2013)
Keywords: Bārūnī, Sulaymān al- (1870-1940)

Riḥlāt al-Bārūnī wa-Atharuhā fī ‘l-Taghyīr al-Ijtimāʿī li-Ḥayāt al-Shuʿūb - Karrūm, Aḥmad Ḥammū (al-Nadwa al-Duwaliyya: Sulaymān Bāshā al-Bārūnī wa-Ḥuḍūruhu fī ‘l-Thaqāfa al-ʿUmāniyya, 10-11 Yūlyū 2012. Buḥūth al-Nadwa, 2013)
Keywords: Bārūnī, Sulaymān al- (1870-1940)

Ṣilāt Sulaymān al-Bārūnī al-Niḍāliyya maʿa Salṭanat ʿUmān khilāl al-Ghazw al-Īṭālī li-Lībiyā - Jabārāt, Maḥmūd Muḥammad al- (al-Nadwa al-Duwaliyya: Sulaymān Bāshā al-Bārūnī wa-Ḥuḍūruhu fī ‘l-Thaqāfa al-ʿUmāniyya, 10-11 Yūlyū 2012. Buḥūth al-Nadwa, 2013)
Keywords: Bārūnī, Sulaymān al- (1870-1940)

Ḥuḍūr al-Shaykh Sulaymān Bāshā al-Bārūnī fī ‘l-Thaqāfa al-ʿUmāniyya: Adabiyyāt Ziyāratihi li-Baldat al-Ḥamrā’... Namūdhajan - ʿIbrī, ʿAlī b. Hilāl al- (al-Nadwa al-Duwaliyya: Sulaymān Bāshā al-Bārūnī wa-Ḥuḍūruhu fī ‘l-Thaqāfa al-ʿUmāniyya, 10-11 Yūlyū 2012. Buḥūth al-Nadwa, 2013)
Keywords: Bārūnī, Sulaymān al- (1870-1940)

Sulaymān Bāshā al-Bārūnī Murabbiyan wa-Muṣliḥan - Ibn Saʿdūn, al-Munīr ʿAbd al-Ḥamīd (al-Nadwa al-Duwaliyya: Sulaymān Bāshā al-Bārūnī wa-Ḥuḍūruhu fī ‘l-Thaqāfa al-ʿUmāniyya, 10-11 Yūlyū 2012. Buḥūth al-Nadwa, 2013)
Keywords: Bārūnī, Sulaymān al- (1870-1940)

Ṣūrat al-Bārūnī fī Shiʿr Abī Salām al-Kindī - Siyābī, Aḥmad b. Saʿūd al- (al-Nadwa al-Duwaliyya: Sulaymān Bāshā al-Bārūnī wa-Ḥuḍūruhu fī ‘l-Thaqāfa al-ʿUmāniyya, 10-11 Yūlyū 2012. Buḥūth al-Nadwa, 2013)
Keywords: Bārūnī, Sulaymān al- (1870-1940)

Malāmiḥ Shakhṣiyyat Sulaymān al-Bārūnī Bāshā min khilāl Majallat al-Minhāj - Yaṭṭū, ʿĀ’isha (al-Nadwa al-Duwaliyya: Sulaymān Bāshā al-Bārūnī wa-Ḥuḍūruhu fī ‘l-Thaqāfa al-ʿUmāniyya, 10-11 Yūlyū 2012. Buḥūth al-Nadwa, 2013)
Keywords: Bārūnī, Sulaymān al- (1870-1940)

Difāʿ al-Mujāhid Sulaymān Bāshā al-Bārūnī ʿan Ḥudūd Lībiyā min khilāl al-Lā’iḥa allatī qaddamahā ilà Ra’īs al-Wuzarā’ al-ʿUthmānī Sanat 1910 - Zarrīqī, Jumʿa Maḥmūd al- (al-Nadwa al-Duwaliyya: Sulaymān Bāshā al-Bārūnī wa-Ḥuḍūruhu fī ‘l-Thaqāfa al-ʿUmāniyya, 10-11 Yūlyū 2012. Buḥūth al-Nadwa, 2013)
Keywords: Bārūnī, Sulaymān al- (1870-1940)

Sulaymān Bāshā al-Bārūnī: Nashāṭuhu ‘l-ʿIlmī wa-Niḍāluhu ‘l-Siyāsī - Zurmān, Aḥmad; Ḥaqāyin, Jumʿa (al-Nadwa al-Duwaliyya: Sulaymān Bāshā al-Bārūnī wa-Ḥuḍūruhu fī ‘l-Thaqāfa al-ʿUmāniyya, 10-11 Yūlyū 2012. Buḥūth al-Nadwa, 2013)
Keywords: Bārūnī, Sulaymān al- (1870-1940)

al-Bārūnī wa’l-Jazā’ir fī Ẓill al-Iḥtilāl al-Faransī - Saʿd Allāh, Abū ‘l-Qāsim (al-Nadwa al-Duwaliyya: Sulaymān Bāshā al-Bārūnī wa-Ḥuḍūruhu fī ‘l-Thaqāfa al-ʿUmāniyya, 10-11 Yūlyū 2012. Buḥūth al-Nadwa, 2013)
Keywords: Bārūnī, Sulaymān al- (1870-1940)

Sulaymān Bāshā al-Bārūnī wa-Nashāṭuhu ‘l-Siyāsī fī ‘l-Mahjar (1924-1940) - Qanāwī, Arwīʿī Muḥammad ʿAlī (al-Nadwa al-Duwaliyya: Sulaymān Bāshā al-Bārūnī wa-Ḥuḍūruhu fī ‘l-Thaqāfa al-ʿUmāniyya, 10-11 Yūlyū 2012. Buḥūth al-Nadwa, 2013)
Keywords: Bārūnī, Sulaymān al- (1870-1940)

Sulaymān Bāshā al-Bārūnī al-Shāʿir al-Faqīh - Qaffa, Qāsim Ḥasan al- (al-Nadwa al-Duwaliyya: Sulaymān Bāshā al-Bārūnī wa-Ḥuḍūruhu fī ‘l-Thaqāfa al-ʿUmāniyya, 10-11 Yūlyū 2012. Buḥūth al-Nadwa, 2013)
Keywords: Bārūnī, Sulaymān al- (1870-1940)

al-Marjaʿiyyāt al-Thaqāfiyya fī Shiʿr al-Bārūnī - Muḥāsana, Muḥammad (al-Nadwa al-Duwaliyya: Sulaymān Bāshā al-Bārūnī wa-Ḥuḍūruhu fī ‘l-Thaqāfa al-ʿUmāniyya, 10-11 Yūlyū 2012. Buḥūth al-Nadwa, 2013)
Keywords: Bārūnī, Sulaymān al- (1870-1940)

Sulaymān al-Bārūnī Adīban wa-Mu’arrikhan - Kuḥḥūlī, Zuhra Saʿdallāwī Ḥaram (al-Nadwa al-Duwaliyya: Sulaymān Bāshā al-Bārūnī wa-Ḥuḍūruhu fī ‘l-Thaqāfa al-ʿUmāniyya, 10-11 Yūlyū 2012. Buḥūth al-Nadwa, 2013)
Keywords: Bārūnī, Sulaymān al- (1870-1940)

al-Rathā’ fī Shiʿr Sulaymān Bāshā al-Bārūnī - Jarrār, ʿAbd al-Rāziq Fāliḥ (al-Nadwa al-Duwaliyya: Sulaymān Bāshā al-Bārūnī wa-Ḥuḍūruhu fī ‘l-Thaqāfa al-ʿUmāniyya, 10-11 Yūlyū 2012. Buḥūth al-Nadwa, 2013)
Keywords: Bārūnī, Sulaymān al- (1870-1940)

al-Su’āl wa-Dalālatuhu fī Shiʿr Sulaymān al-Bārūnī (Dirāsa fī ‘l-Adawāt) - Hindī, ʿAlī al- (al-Nadwa al-Duwaliyya: Sulaymān Bāshā al-Bārūnī wa-Ḥuḍūruhu fī ‘l-Thaqāfa al-ʿUmāniyya, 10-11 Yūlyū 2012. Buḥūth al-Nadwa, 2013)
Keywords: Bārūnī, Sulaymān al- (1870-1940)

al-Dawr al-Siyāsī li’l-Shaykh al-Bārūnī min khilāl Majlis al-Maʿbūthān - Hāzil, ʿAlī ʿUmar al- (al-Nadwa al-Duwaliyya: Sulaymān Bāshā al-Bārūnī wa-Ḥuḍūruhu fī ‘l-Thaqāfa al-ʿUmāniyya, 10-11 Yūlyū 2012. Buḥūth al-Nadwa, 2013)
Keywords: Bārūnī, Sulaymān al- (1870-1940)

Ḥuḍūr al-Bārūnī fī ‘l-Shiʿr al-ʿUmānī bayna Ṣūrat al-Mujāhid wa-Shakhṣiyyat al-Muṣliḥ - Ḥajarī, Muḥammad b. Saʿīd b. ʿĀmir al- (al-Nadwa al-Duwaliyya: Sulaymān Bāshā al-Bārūnī wa-Ḥuḍūruhu fī ‘l-Thaqāfa al-ʿUmāniyya, 10-11 Yūlyū 2012. Buḥūth al-Nadwa, 2013)
Keywords: Bārūnī, Sulaymān al- (1870-1940)

Mawqif Īṭāliyā min Anshiṭat Sulaymān al-Bārūnī, 1914-1924 - Ghawīṭa, Miftāḥ Balʿīd (al-Nadwa al-Duwaliyya: Sulaymān Bāshā al-Bārūnī wa-Ḥuḍūruhu fī ‘l-Thaqāfa al-ʿUmāniyya, 10-11 Yūlyū 2012. Buḥūth al-Nadwa, 2013)
Keywords: Bārūnī, Sulaymān al- (1870-1940)

Khilāf Sulaymān Bāshā al-Bārūnī maʿa ‘l-Amīr Shakīb Arslān wa-Mawqif al-Shaykh ʿAbd al-Ḥamīd b. Bādīs minhu - Fāyd, Bashīr (al-Nadwa al-Duwaliyya: Sulaymān Bāshā al-Bārūnī wa-Ḥuḍūruhu fī ‘l-Thaqāfa al-ʿUmāniyya, 10-11 Yūlyū 2012. Buḥūth al-Nadwa, 2013)
Keywords: Bārūnī, Sulaymān al- (1870-1940)

Mawāqif al-Bārūnī fī ‘l-Aḥdāth al-Maḥalliyya wa’l-ʿĀlamiyya bi-Baghdād, 1931-1937 - Bahjat, Mujāhid Muṣṭafà; Ṣaqrī, Saʿīd b. ʿAbd Allāh b. Sallām al- (al-Nadwa al-Duwaliyya: Sulaymān Bāshā al-Bārūnī wa-Ḥuḍūruhu fī ‘l-Thaqāfa al-ʿUmāniyya, 10-11 Yūlyū 2012. Buḥūth al-Nadwa, 2013)
Keywords: Bārūnī, Sulaymān al- (1870-1940)

Dawr al-Shaykh Sulaymān al-Bārūnī fī Muwājahat al-Istiʿmār al-Īṭālī - ʿĀshūrī, Qamʿūn (al-Nadwa al-Duwaliyya: Sulaymān Bāshā al-Bārūnī wa-Ḥuḍūruhu fī ‘l-Thaqāfa al-ʿUmāniyya, 10-11 Yūlyū 2012. Buḥūth al-Nadwa, 2013)
Keywords: Bārūnī, Sulaymān al- (1870-1940)

Mawqif al-ʿĀlim al-Mujāhid Sulaymān al-Bārūnī min Mas’alat Ilghā’ al-Khilāfa al-ʿUthmāniyya ʿĀm 1924 M., - ʿĀlim, ʿIzz al-Dīn ʿAbd al-Salām al- (al-Nadwa al-Duwaliyya: Sulaymān Bāshā al-Bārūnī wa-Ḥuḍūruhu fī ‘l-Thaqāfa al-ʿUmāniyya, 10-11 Yūlyū 2012. Buḥūth al-Nadwa, 2013)
Keywords: Bārūnī, Sulaymān al- (1870-1940)

al-Abʿād al-Fikriyya wa’l-Falsafiyya wa’l-Adabiyya fī Kitābāt Sulaymān al-Bārūnī - Abū ʿAlūsh, Ibrāhīm Muḥammad; Ḥarāḥasha, Aḥmad al- (al-Nadwa al-Duwaliyya: Sulaymān Bāshā al-Bārūnī wa-Ḥuḍūruhu fī ‘l-Thaqāfa al-ʿUmāniyya, 10-11 Yūlyū 2012. Buḥūth al-Nadwa, 2013)
Keywords: Bārūnī, Sulaymān al- (1870-1940)

Sulaymān al-Bārūnī: Dawruhu fī Maydān al-Jihād wa-Ta’sīs al-Jumhūriyya al-Ṭarāblusiyya (1873-1940) - ʿAbd, Aḥmad Ḥusayn; ʿAlī, Munà Jalāl (al-Nadwa al-Duwaliyya: Sulaymān Bāshā al-Bārūnī wa-Ḥuḍūruhu fī ‘l-Thaqāfa al-ʿUmāniyya, 10-11 Yūlyū 2012. Buḥūth al-Nadwa, 2013)
Keywords: Bārūnī, Sulaymān al- (1870-1940)

al-Nadwa al-Duwaliyya: Sulaymān Bāshā al-Bārūnī wa-Ḥuḍūruhu fī ‘l-Thaqāfa al-ʿUmāniyya, 10-11 Yūlyū 2012. Buḥūth al-Nadwa - Jālūdī, ʿUlayyān; Muqābila, Kamāl; Ḥarāḥasha, Aḥmad al- (Sultan Qaboos University, 2013)
Keywords: Bārūnī, Sulaymān al- (1870-1940)

فقه الإمام أبي عبدالله محمد بن محبوب العماني (ت:260هـ) : جمع وترتيب ودراسة - الحوسني, شمسة بنت عبد الله (جامعة القاهرة, 2013)
Keywords: Fiqh

البحوث الجيومرفولوجية ودورها في ترشيد التهيئة بالقطر التونسي: جزيرة جربة نموذجا - بورقو, المنجي (الحياة الثقافية, 2013)

المصوغ التقليدي بجربة اثر مفنوح - الفقيلي, هدى (الحياة الثقافية, 2013)
Keywords: Artisanat -- Djerba

جربة والتجارة المتوسطية في عهد البوني موقع غيزن مثلا - بن طاهر, سامي (الحياة الثقافية, 2013)
Keywords: Archéologie -- Djerba

al-Tajribah al-dustūrīyah fī ʻUmān =: Constitutional experience of Oman - Said, Basma Mubarak (Markaz Dirāsāt al-Waḥda al-ʻArabīyah, 2013)

ʻUmān, al-insān wa-al-sulṭah: qirāʼah mumahhadah li-fahm al-mashhad al-siyāsī al-ʻUmānī al-muʻāṣir - Hāshimī, Saʻīd ibn Sulṭān (Markaz Dirāsāt al-Waḥdah al-ʻArabīyah, 2013)

The Aterian from the Jebel Gharbi (Libya): New Technological Perspectives from North Africa - Spinapolice, Enza E.; Garcea, Elena (The African Archaeological Review, 2013)
Keywords: Archéologie -- Djebel Nefousa

From Musaylima to the Khārijite Najdiyya - Makin, Al (Al-Jami'ah: Journal of Islamic Studies, 2013)
This paper tries to reconstruct the following accounts: the defeat of Musaylima and the death of his prominent followers, and the rise of the Khārijite Najdiyya in Yamama. Moreover, this study seeks the evidence which points to the possible connection between Musaylima’s movement and the Khārijite Najdiyya. This paper highlights that many founders and prominent leaders of the Khārijites, and particularly the Najdiyya sect, came from the tribe of Ḥanīfa, to which Musaylima belonged. This, among other things, seems to have become the main impulse of attraction for the people of Ḥanīfa to join the sect. Additionally, the ‘characteristics’ and the ‘image’ of the Najdiyya reflect those of Musaylima. This leads us to conjecture that the people of Ḥanīfa, having failed to defend their prophet Musaylima and the land of Yamāma against the Medinan caliphate under Abū Bakr in the Battle of ‘Aqraba, later joined the Khārijite Najdiyya. [Artikel ini menjelaskan kekalahan Musaylima dan kematian pengikut-pengikut utamanya serta kemunculan aliran Khawārij Najdiyya di Yamāma. Melalui artikel ini, penulis membuktikan relasi antara gerakan Musaylima dan Khawārij Najdiyya. Ini bisa dibuktikan dengan mencermati fakta bahwa sebagian pendiri dan tokoh utama Khawārij, utamanya sekte Najdiyya, berasal dari suku Ḥanīfa suku yang juga menjadi asal muasal Musaylima. Kesamaan suku inilah dan beberapa faktor lainnya nampaknya menjadi daya tarik tersendiri bagi orang-orang suku Ḥanīfa untuk bergabung dengan sekte Najdiyya. Selain itu, ‘karakteristik’ dan ‘imej’ sekte Najdiyya yang menyerupai gerakan Musaylima adalah hal lain yang turut menguatkan asumsi tersebut. Pandangan inilah yang kemudian mengantarkan penulis pada kesimpulan bahwa setelah gagal mempertahankan nabi mereka, Musaylima, dan wilayah mereka, Yamāma, melawan khilafah Islam di Madinah yang dipimpin Abū Bakr, suku Ḥanīfa memilih memberontak dan bergabung dengan sekte Khawārij Najdiyya.]
Keywords: Kharijisme

Buraimi: the struggle for power, influence and oil in Arabia - Morton, Michael Quentin (I.B. Tauris, 2013)
"Buraimi is an oasis in an otherwise bleak desert on the border between Oman and the UAE. In the early twentieth century, it shot to notoriety as oil brought the world's attention to this corner of the Arabian Peninsula, and the ensuing battle over energy resources between regional and global superpowers began. In this lively account, Michael Quentin Morton tells the story of how the power of oil and the conflicting interests of the declining British Empire and the United States all came to a head with the conflict between Great Britain and Saudi Arabia, shaping the very future of the Gulf states. The seeds of conflict over Buraimi were sown during the oil negotiations of 1933 in Jedda, where the international oil companies vied for control of the future industry in the Arabian Peninsula. As a result of lengthy discussions, including the efforts of men such as St John Philby and Ibn Saud himself, the Saudis granted an oil concession for Eastern Arabia without precisely defining the geographical limits of the area to be conceded. Matters came to a head in 1949 when Saudi Arabia made claim to the territory, and Great Britain, acting on behalf of Oman and Abu Dhabi, challenged the actions of the Saudis. Attempts at arbitration failed, and only one year before Britain's defeat over the Suez Canal, Britain expelled Saudi Arabia from the oasis. In the wake of Britain's withdrawal 'East of Suez' in the early 1970s, the dispute was apparently solved between Saudi Arabia and the UAE. But whilst the controversy dominated Anglo-Saudi relations for more than 30 years, it still casts its shadow across the Gulf today, threatening to expose the fragility of the West's ever-present dependency on the region for its supply of oil. Morton brings a range of historical figures to life, from the American oilmen arriving in steamy Jedda in the 1930s, to the rival sheikhs of Buraimi itself competing for power, wealth and allegiances as well as the great players in world politics: Churchill, Truman and Ibn Saud. This entertaining and thoroughly researched book is both a story of a decisive conflict in the history of Middle East politics and also of the great changes that the discovery of oil brought to this previously desolate land." Présentation de l'éditeur
Keywords: Relations -- Oman -- Arabie Saoudite

al-Ḥayāt al-ʻilmīyah bi-Umān fī ʻahd al-Yaʻāribah, 1034 H / 1624 M ilá 1157 H 1744 M - Barāshidī, Musá ibn Sālim ibn Ḥamad (Dār al-Farqad lil-Ṭibāʻah wa-al-Nashr wa-al-Tawzīʻ, 2013)
Keywords: Vie politique -- Oman -- 1624-1742

Social and gender inequality in Oman: the power of religious and political tradition - Azri, Khalid al- (Durham modern Middle East and Islamic world series, 2013)

Travelling through time: essays in honour of Kaj Öhrnberg - Öhrnberg, Kaj; Akar, Sylvia; Hämeen-Anttila, Jaakko; Nokso-Koivisto, Inka (Studia Orientalia / the Finnish Oriental Society, 2013)

“The Other” among us: the perception of Khārijī and Ibāḍī Islam in the Muslim exegetical traditions - Albayrak, Ismail (Ankara Üniversitesi Ilâhiyat Fakültesi Dergisi, 2013)
Keywords: Kharijisme

Analyse d'un lexique berbère =: Tajeṛṛumt d umawal - Mammeri, Boussad (Mémoires du Centre National de Recherches Préhistoriques Anthropologiques et Historiques, 2013)
Keywords: Linguistique

Les innovations de Naffāṯ b. Naṣr ou le troisième schisme chez les ibadites - Prevost, Virginie (Al-Qantara : Revista de Estudios Arabes, 2013)
Keywords: Naffathisme

Valerie J. Hoffman, The Essentials of Ibāḍī Islam, Syracuse, Syracuse University Press, 2012, xii+344 p., ISBN : 978-0-8156-3288-7, 32,47 € (relié). - Prevost, Virginie (Arabica, 2013)
Keywords: Recension

Democracy and youth in the Middle East: Islam, tribalism and the rentier state in Oman - Farsi, Sulaiman H. al- (Library of modern Middle East studies, 2013)
"The leaders of the oil-rich rentier states of the Middle East, and in particular in the Gulf, have hitherto often predicated their legitimacy on a tacit social contract with their (much poorer) populations. This social contract consists of little or no direct taxation, with some sort of subsidised living. But the casualty of this tacit agreement is often political participation, an issue which has come to the forefront in the Middle East following the 'Arab Spring' of 2011. Here, Sulaiman Al-Farsi looks at the impact the rentier nature of the Gulf States has on political participation, focusing on the nexus between tribe, religion and a new generation of young, highly educated citizens that is present in Oman. Specifically exploring the concept of shura (consultation), and how nascent concepts of democracy in the practice of shura have impacted and shaped the process of democratisation, Al-Farsi's book is vital in the examination of the political discourse surrounding democratisation across one of the most strategically important, but little understood states in the Middle East."--Publisher's website

Regionalizing Oman: Political, Economic and Social Dynamics - Wippel, Steffen (United Nations University Series on Regionalism, 2013)
This volume addresses the historical structures and current dynamics of Oman's regionalization processes and their political, economic and social dimensions. It is based on an interdisciplinary and trans-regional dialogue between scholars from different social sciences and area studies such as political science, economics, management, economic and social geography, history, social anthropology and linguistics as well as Middle East/West Asian, gulf and African studies, and develops four major axes of research: - Oman's integration into global and regional flows of goods, capital, people and ideas; - The multi-scaled political negotiation of such integration (or disintegration) processes; - Consequences of suchlike processes and forms of regionalization for (translocal) actors; - Ideas and strategic communication of regional belonging and the constitution of regions. Each chapter deals with one or more of these issues. Part I deals with concepts of regionalisation and region-building and presents different approaches that accentuate certain dimensions of these processes and come from different disciplinary backgrounds. Part II focuses on the translocal, transnational and (trans)regional movement of people, their practices and imaginations, be they contemporary labour in- and out-migrants, returnees from Eastern Africa or nomadic tribal members. Part III takes a closer look particularly at economic issues and regionalisation processes that are mainly based on multiple trade links, regional development policies or politics of regionalism. Part IV analyses political and socio-cultural issues in regional and global perspectives

المعتمد في فقه الحج و العمرة: دليلك الموثق و كتابك المنهجي على آراء الشيخين الجليلين: أحمد بن حمد الخليلي و سعيد بن مبروك القنوبي - المعولي, المعتصم بن سعيد (المعتمد, 2013)
Keywords: Fiqh; Fiqh -- Oman -- 2000-....

المعتمد في فقه العمرة :‏ ‏دليلك الموثق وكتابك المنهجي على آراء الشيخين الجليلين: أحمد بن حمد الخليلي و سعيد بن مبروك القنوبي - المعولي, المعتصم بن سعيد (نشر المؤلف, 2013)
Keywords: Fiqh

أضواء إسلامية على المعالم الإباضية :‏ ‏بيانها، حقائقها، تاريخها - أعوشت, بكير بن سعيد (مكتبة الضامري, 2013)

الإباضية في مرآة علماء الإسلام قديما وحديثا - أعوشت, بكير بن سعيد (مكتبة الضامري, 2013)

الصفات النفسية لسماحة الشيخ أحمد بن حمد الخليلي من خلال نتاجه الفكري - البوصافي, سالم بن راشد (نشر المؤلف, 2013)

الفتاوى: العقيدة - الخليلي, أحمد بن حمد (مكتبة الاجيال, 2013)
Keywords: Fatwas -- Oman -- 2000-....

لطيف الحوار على بهجة الانوار: شرح منظومة أنوار العقول للإمام نور الدين السالمي - الكندي, مهنا بن سليمان (مكتبة الجيل الواعد, 2013)

الدرجيني و منهجه في كتاب طبقات المشائخ بالمغرب - الريامي, علي بن سعيد (‏الجامعة الأردنية, 2013)
Keywords: Prosopographie -- Afrique du Nord

القبيلة ودورها في الحياة السياسية في عمان (1219 هـ / 1804 - 1305 هـ / 1888 م) - السعدي, ناصر بن سيف (جامعة السلطان قابوس, 2013)

أبو زيد عبد الله بن محمد الريامي :‏ ‏السيرة و الآثار و الأعمال - مكتبة الندوة العامة (مكتبة الندوة العامة, 2013)

من روائع السلف الصالح :‏ ‏حكم وأقوال ووصايا وآراء وفتاوى ومواقف لعلماء أهل الحق والاستقامة: الحلقة الأولى من القرن الأول إلى القرن السادس من الهجرة - السابعي, ناصر بن سليمان (2013)
Keywords: Fiqh; Fiqh -- Ibadisme

الفكر السياسي عند الإمام السالمي :‏ ‏دراسة تحليلية - الريامي, عبد الله بن سليمان (الجامعة الإسلامية العالمية, 2013)

الدين والدولة في الفكر الإباضي - عرب, محمد صابر (دار الشروق, 2013)

إمام العلم و العمل: الشيخ الرضي حمود بن حميد الصوافي :سيرة حياة - الصوافي, سالم بن مسعود (رؤى, 2013)

سليمان باشا الباروني: أمة في رجل - الشيباني, سليمان بن سعيد (جمعية الفتح للدراسات الاباضية, 2013)

مدرسة الإمام محمد بن عبد الله الخليلي و أثرها في نشر العلم - الشكيلي, إبراهيم بن محمد (نشر المؤلف, 2013)

الندوة الدولية :‏ ‏سليمان باشا الباروني و حضوره في الثقافة العمانية، 10-11 يوليو 2012 م. - مركز الدراسات العمانية (جامعة السلطان قابوس, 2013)

الإباضية :‏ ‏مذهب إسلامي معتدل - معمر, علي يحيى (دار الحكمة, 2013)
Keywords: Ouvrages de vulgarisation

الدلائل على اللوازم والوسائل - المحروقي, درويش بن جمعة (مكتبة الضامري, 2013)
Keywords: Foi -- Traité -- 17e siècle

مائة كتاب أباضي - إمام, محمد كمال الدين (وزارة الأوقاف والشؤون الدينية, 2013)
Keywords: Recension

الإباضية بين حراسة الدين و سياسة الدنيا - الأغبري, إسماعيل بن صالح (وزارة الأوقاف والشؤون الدينية, 2013)

الخلاصة في فقه المعاملات المالية عند الإباضية - الكندي, ماجد بن محمد (وزارة الأوقاف والشؤون الدينية, 2013)
Keywords: Fiqh

بداية المجتهد و نهاية المقتصد :‏ ‏مع الراجح من أراء المذهب الإباضي و فقه المذاهب الإسلامية - ابن رشد, محمد بن أحمد (وزارة الأوقاف والشؤون الدينية, 2013)
Keywords: Fiqh

شرح غاية المراد في نظم الإعتقاد - الخليلي, أحمد بن حمد (وزارة الأوقاف والشؤون الدينية, 2013)

المدخل إلى الفقه الإباضي - الأغبري, إسماعيل بن صالح (مكتبة الضامري, 2013)
Keywords: Fiqh

القواعد الفقهية عند الإباضية: دراسة نظرية تحليلية تأصيلية تطبيقية - أرشوم, مصطفى بن حمو (‏سلسلة القواعد الفقهية الإباضية, 2013)
Keywords: Fiqh

الخوارج: الامتداد الفكري بين الأزارقة و الوهابية - السيابي, زاهر بن سعود (مكتبة الضامري, 2013)
Keywords: Kharijisme

الباب لمعرفة تاريخ الأصحاب :‏‏ ‏التاريخ الإباضي بأسلوب قصصي ميسر - السيابي, زاهر بن سعود (التاريخ الإباضي بأسلوب قصصي, 2013)

رسائل الإمام جابر بن زيد الأزدي و هي ثمانية عشرة رسالة - الأزدي, جابر بن زيد (مكتبة الضامري, 2013)

حقيقة الإباضية و عقيدتهم - المسقري, ناصر بن مطر (مكتبة و تسجيلات الهلال الإسلامية, 2013)

الوجيز في فقه المعاملات المالية عند الإباضية - الكندي, ماجد بن محمد (من حلقات الدروس العلمية ببهلا, 2013)
Keywords: Fiqh

تنفست نلميراز: مقدّمات لدراسة الأمازيغيّة التونسيّة المعاصرة - بن معمر, فتحي (مكتبة تونس, 2013)
Keywords: Littérature -- Djerba

The Problems Encounter Teachers in Teaching Translation: Case Study Nafousa Mountain University Libya - Hammad, Suad Arebi (جامعة أم درمان الاسلامية, 2013)
Keywords: Linguistique -- Djebel Nefousa

عوامل ازدهار الفلاحة فی جبل نفوسة من القرن الثانی الهجری/ الثامن المیلادی حتى نهایة القرن الرابع الهجری /العاشر المیلادی - حدود, منى علی (حولیات کلیة الآداب جامعة عین شمس, 2013)
ركزت الدراسات التاريخية على الناحية السياسية والعسكرية والإدارية بشكل كبير , وما يرتبط بذلك من الاهتمام بالحروب وعوامل النصر والهزيمة. فضلاً عن اهتمامها بسير الأفراد وتطور الأحداث. إلى أن بدأ الاهتمام يتجه نحو دراسة الشعوب وتسليط الضوء على النواحي الاجتماعية والاقتصادية والعلمية.

خطب الخوارج ومضامينها العقدية والفكرية - الماجد, سعد بن عبدالله بن سعد (مجلة الدراسات العقدية, 2013)
Keywords: Kharijisme

الخوارج وتأويلاتهم المنحرفة لآيات القرآن الكريم وتفنيدها - حسن, سامي عطا (المجلة الأردنية في الدراسات الإسلامية, 2013)
Keywords: Kharijisme

جهود المفسرين في الرد على الخوارج - الحسيني, عمر بن مبيريك بن حذيفة (الجامعة الإسلامية بالمدينة المنورة, 2013)
Keywords: Kharijisme

في فكر الخوارج الكتاب والسنة في شعار " لاحكم إلا لله " - الراميني, عرسان (المجلة الأردنية في اللغة العربية وآدابها, 2013)
ينطوي هذا المقال على محاولة لتقديم تفسير جديد لشعار الخوارج: "لا حكم إلا لله". فالتفسير التقليدي لهذا الشعار يرى فيه دعوة إلى تحكيم القرآن الكريم في النزاع بين علي ومعاوية رضي الله عنهما، دون تدخل البشر. في المقابل، يرى المقال الحالي أن الرفض المتضمن في الشعار لم يكن موجها لتحكيم البشر في ذلك النزاع بقدر ما كان موجها لتحكيم "السنة" واتخاذها مرجعية في الفصل في النزاع إلى جانب مرجعية القرآن. وفي الدفاع عن هذا الفهم الجديد للشعار، يؤكد المقال ابتداء أن القضية المحورية للمعارضة العراقية للسلطة المركزية في المدينة إنما تمثلت في السياسات المالية للخليفة عثمان رضي الله عنه. ثم، بعد ذلك، يتناول المقال جوانب معينة، أولا، في سنة النبي عليه السلام، وثانيا، في سنة عمر بن الخطاب رضي الله عنه، حتى يبين أن سنتهما قد اشتملت بالفعل على ما من شأنه أن يضفي شرعية على إجراءات اتخذها عثمان فيما يخص الفيء، أو توزيع عوائد الفتوح، لكنها رفضت بشدة من جانب الخوارج، الذين كانوا آنذاك يمثلون أكثر أطراف المعارضة تشددا. ومادام التحكيم سيفضي إلى إصدار حكم يحدد ما إذا كان عثمان قد قتل مظلوما أو غير مظلوم، ويقرر، من ثم، مصير كل المتورطين في قتله، فإن الرجوع إلى السنة سيكون، في هذه الحالة، مرفوضا من الخوارج؛ ولذلك، طالبوا بأن يكون القرآن هو المرجعية الوحيدة في التحكيم.
Keywords: Kharijisme

صورة الآخر في أدب الخوارج : صراعهم مع الإمام علي بن أبي طالب (عليه السلام) مثالاً - الساعدي, عباس عبيد (مجلة آداب المستنصرية, 2013)
مثل الآخر مشكلة في الرؤية الثقافية العربية لاسيما عند التأصيل على الرغم من الموقف الحضاري للقرآن الذي شدد في كثير من سوره على ضرورة الالتقاء بالآخر ومحاورته، بل ومشاورته والنزول عند رأيه إذا كان راجحاً قوياً، فإذا كانت الدعوة القرآنية على هذا النحو لما وجدنا هذه القطيعة والنظرة العدائية للآخر والتي تبلورت على يد فرقة إسلامية لها أثر كبير فيما آلت إليه حضارة الدولة الإسلامية، و لما صار هذا الكره الذي استوطن الروح الخارجية اتجاه الآخر شيعياً كان أو أموياً أو عباسياً، يا ترى هل هي قيم البداوة والقبلية التي تأصلت في نفوسهم أم عقدة الحكم وما آلت إليه بعد التحكيم ؟ أسئلة كثيرة لاشك في أن النص الخارجي بعد استنباطه سيجيب عن كثير منها. ‏‏ إن مواجهة الآخر كانت وستظل ديدن الاختلاف والمهم في الأمر أنهم حينما واجهوا الآخر ظلوا مصرين على الاكتراث به لكنهم لم يحاولوا في الوقت نفسه التعرف عليه وتفهمه بدلاً من ذلك الصراع المر الذي دار على امتداد التاريخ الإسلامي، والتهم أمما في حروب طاحنة ونيران مستعرة، وثارات لا تخمد أحقادها وضغائنها. ‏ إن الثبات الفكري الذي قام عليه فكر الخوارج الاعتقادي والذي انعكس على أدبهم؛ يعد مفصلاً مهماً في ثقافتهم التي اتكأت على الأصول، فشكل انشقاقهم مرحلة حاسمة في الصراع بين التبات والتحول، فكانت هزيمة الرؤية التي ترى الانفتاح على الثقافات الأخرى وعدم الانغلاق على رؤية واحدة إيذاناً بانهيار ثقافة التعدد وبروز الوجه الآخر المعادي لكل ما لا يتفق ورؤيتهم، فعدم استيعاب الخوارج للجوهر الحقيقي للرسالة الإسلامية وتمسكهم بسطحية النص على وفق رؤية ضيقة جداً وضعتهم في زاوية الجهل بالدين والتبجيل الأعمى له، وأحياناً الشطط أو التعسف في الفهم والتأويل. ‏ يتضح من خلال النصوص التي سنقف عندها عمق الصراع الثقافي بين الرؤى المختلفة الاتجاه حداً وصلت فيه إلى الاحتراب بالسيف فكان النص الخارجي ديدن البحث في الوقوف على تلك الرؤى لاستبانة صورة الآخر في ثقافتهم التي هي جزء من الثقافة العربية القديمة.
Keywords: Kharijisme

موقف الفرق الإسلامية من الخليفة عثمان بن عفان رضي الله عنه - شبيب, نايف محمد (بحوث الندوة العلمية: ذو النورين عثمان بن عفان رضي الله عنه صحبة صادقة وخلافة راشدة, 2013)
من المعلوم لدى الباحثين في التاريخ الإسلامي أن فتنة مقتل الخليفة الراشدي الثالث عثمان بن عفان رضي الله عنه سنة: عنه 35 ه كانت أعظم فتنة تصيب المسلمين بعد وفاة الرسول صلى الله عليه وسلم، إذ كانت مدة خلافته اثنا عشرة سنة، وعلى الرغم من أنه من المبشرين بالجبنة والأحاديث التي وردت في فضله كثيرة جدا، إلا أن هناك من المسلمين من رأى فيه رأيا آخر، ولا سيما بعض الفرق الإسلامية التي تذبذب موقفها منه رضي الله عنه، فالبعض لم يرض بخلافته كلها، والبعض كفره، والبعض قسم خلافته قسمين، رضي عنه في القسم الأول (ست سنوات) ولم يرض عنه في القسم الثاني السنوات الست الأخرى، وفي هذه الورقة سوف نسلط الضوء على موقف هذه الفرق ( الخوارج، الشيعة، المعتزلة، المرجئة...) من هذا الخليفة الراشدي، ومن ثم بيان سبب هذه المواقف والرد عليها وتفنيدها.

نسب الولد بين مذاهب أهل السنه والإباضية - عبد الجواد, عبد الجواد خلف محمد (مجلة التربية, 2013)
يعني هذا البحث بأهم الأحكام المتعلقة بالأولاد في نظر الشريعة الإسلامية، ومجمل قوانين الأحوال الشخصية الوضعية في بعض البلاد العربية مع التركيز على آراء فقهاء أهل السنة وفقهاء المذهب الإباضي فيما يتعلق بنسب الأولاد وقد انتظم البحث في خطته على النحو التالي: خطة البحث يقع هذا البحث: "نسب الولد" بين مذاهب أهل السنة والإباضية في خمسة مطالب، وخاتمة مذيلة بمصادر البحث ومراجعه على النحو التالي: المطلب الأول: تعريف النسب. المطلب الثاني: أسباب النسب، ومن ينسب إليه الولد. المطلب الثالث: شروط ثبوت النسب. المطلب الرابع: مسائل النسب. المطلب الخامس: مسائل ثبوت النسب أثناء العدة الخاتمة وأهم النتائج: المصادر والمراجع.

نظرة حول نشأة و تطور مدينة تاهرت - بويحياوي, عز الدين (فعاليات الملتقى الدولي الثاني: العمران والعمارة في المتوسط خلال العهدين القديم والوسيط في ضوء المصادر الأثرية والأدبية, 2013)
Keywords: Urbanisme -- Tahert

حضانة الولد بين مذاهب أهل السنة والإباضية - عبد الجواد, عبد الجواد خلف محمد (مجلة التربية, 2013)
يعني هذا البحث بأهم الأحكام المتعلقة بحضانة الولد في نظر الشريعة الإسلامية، وما استمدته منها قوانين الأحوال الشخصية في بعض البلاد العربية مع التركيز على آراء فقهاء مذاهب أهل السنة والمذهب الإباضي فيما يتعلق بحق الحضانة، ومدتها، والتنازل عنها، واستحقاق الأجرة عليها، ومدتها، ومكانها، وما يجب على الحاضن تجاه المحضون.

الصلات الاقتصادية والدبلوماسية بين المغرب الأوسط والسودان الغربي وأثرها على الحياة الثقافية بين القرنين الثاني والثالث الهجريين - مسعود, خالدي (دورية كان التاريخية, 2013)
يتناول المقال بداية الصلات بين المغرب الأوسط والسودان الغربي، حيث كانت العلاقات في مجملها تجارية في عهد الولاة وفي فترة حكم الرستميين، وعلى إثرها أقيمت علاقات سياسية تجلت مظاهرها في الوفود الدبلوماسية التي أرسلتها الدولة الرستمية لبلاد السودان منها بعثة محمد بن عرفة، وقد بينت الدراسة آثار الاتصال بين تجار الدولة الرستمية وأهالي السودان الغربي في الحياة الثقافية، فقد انتشر الإسلام ومعه المذهب الأباضي واللغة العربية والعادات والتقاليد الإسلامية كما تجلى الأثر الثقافي في المجال العمراني حسب ما توصل إليه عالم الآثار شاخت.
Keywords: Commerce transsaharien

تأويل الخطاب الإباضي بين التزام النص وحجية إعمال الرأي : مقاربة في المقاولات الكلامية - عزاب, عبدالرحيم (مجلة العلوم الإجتماعية, 2013)
تسعى هذه الدراسة إلى التعريف بالمنهجية النظرية الاستدلالية التي استخدمها المذهب الإباضي من خلال المباحث المتعلقة بأصول العقيدة الإسلامية وأركانها المعروضة في أجل مضانها العلمية. تحت عنوان: تأويل الخطاب الإباضي بين التزام النص وحجية إعمال الرأي مقاربة في المقولات الكلامية -وقد قسمت هذه الدراسة إلى مستويات ثلاثة، هي: المفهوم الإبستيمي للإباضية من حيث الاشتقاق اللغوي والمسرد التاريخي. مراحل التأسيس والشخصيات المرجعية. مدخل إلى العقائد الدينية والفكرية للإباضية في ضوء نظريات علم الكلام. وقد اقتضت الدراسة الاتكاء على النظرة النقدية وفق المنهج التحليلي التفسيري.

إجراءات الإثبات بالشهادة في المعاملات المدنية والتجارية من منظور القانون العماني والفقه الإباضي - التوبي, يزن بن سيف بن محمد (جامعة السلطان قابوس, 2013)

التبديع والتكفير في الخطاب الاباضي الأصولي : الوارجلاني (ت 570هـ / 1175م) والخليلي انموذجاً - الجلاصي, بثينة (أشغال الندوة العلمية الدولية: المد المذهبي المعاصر, 2013)

التنظيمات الفرنسية للجماعات الحرفية والإثنية غداة الاحتلال : حالة جماعة بني مزاب - ناصر, بالحاج بن باحمد (مجلة العلوم الإنسانية, 2013)
يهدف هذا المقال إلى تبيين بعض حيثيات السياسة التي اتبعتها الإدارة الفرنسية اتجاه التنظيمات العثمانية للطوائف الحرفية والإثنية، بعد سقوط مدينة الجزائر في 05 جويلية 1830، هذه الطوائف التي لم تجد من جهتها خيارا غير التعامل مع الاحتلال الذي أصبح أمرا واقعا لا بد من التكيفّ معه، لكن زعاماتها وقعت في تناقضات كبيرة جراء الدور الجديد الذي أصبحت مجبرة على القيام به. وعندما لم تعد الإدارة بحاجة إلى هذه التنظيمات، نسفتها واستغنت عنها بشكل نهائي.

نشأة الحركة الإباضية‏‏ - خليفات, عوض محمد (دار الحكمة, 2013)

المذهبي والتاريخي والنقدي في تيسير التفسير الإباضي - بوعجيلة, فتحي (نشر المؤلف, 2013)
Keywords: Coran -- Commentaires -- 19e siècle

أحكام القانون الدولي والعلاقات الدولية في الفقه الأباضي - أبو الوفا, أحمد (وزارة الأوقاف والشؤون الدينية, 2013)
Keywords: Droit -- Oman; Fiqh

تاريخ الأباضية الديني والسياسي من القرن الأول إلى القرن السادس هجري - قوجة, المنصف (الدار التونسية للكتاب, 2013)
Keywords: Idées politiques -- Ibadisme

الإباضية أصولها وأعلامها وأثرها في التقريب بين المذاهب الإسلامية - الشيباني, طارق ساسي (إيسيسكو, 2013)

تاريخ إباضية تمازغا: مقدمة في تاريخ الإباضية ببلاد المغرب في القرون الهجرية الأولى - الشيباني, محمد سعد (نشر المؤلف, 2013)
Keywords: Ibadisme -- Afrique du Nord; Monuments -- Djerba; Sidi Salih, mosquée (Bani Bandou, Djerba); Tîwâjin, mosquée (Tîwâjin, Djerba)

الرد على المعتزلة والخوارج والمرجئة ...أو الرد على جميع المخالفين - الوسياني, أبو خزر يغلا بن زلتاف (دار ياسين, 2013)
Keywords: Foi -- Traité -- 10e siècle

تاريخ جربة وعلمائها - بن يعقوب, سالم (سيلدار, 2013)
Keywords: Monuments -- Djerba; Sidī Yaʿīsh, mosquée (Jaabira, Djerba); Walḥī, mosquée (Oued Zbib, Djerba)

Intellectual Traditions, Islamic Reform and Nationalism in the Mzab - Ghazal, Amal N. (THE SOUTHERN SHORES OF THE MEDITERRANEAN AND BEYOND: 1800 - TO PRESENT, 2013)
This paper discusses the role of North African Ibadis, Mzabis in particular, in movements of religious reform and nationalism in the nineteenth and twentieth centuries. It unravels the intellectual networks in which Mzabis had been integrated since the late nineteenth century and that spanned from North Africa to East Africa and Oman. Mzabis’ membership in such networks highlighted the reformist trends within Ibadism that led to a rapprochement with the other sects of Islam. This also consequently facilitated the assimilation of Mzab and of Mzabis into the nationalist movements of Algeria in which Mzabis played a leading and formative role. Sources include manuscripts from the Mzab valley, Mzabi newspapers and French archival material.
Keywords: Réformisme -- Mzab

Antécédent et conséquences du capital marque d’une destination sur les réponses attitudinales et comportementales des touristes cas de l’île de Djerba - Ben Hariz, Atef (Institut supérieure de gestion, 2013)
Keywords: Tourisme -- Djerba

معطيات جديدة عن أصول الإباضية وإقامة المذهب - Prevost, Virginie (التفاهم, 2013)

علم الكلام الإباضي بشمال إفريقيا - الشيخ, محمد (التفاهم, 2013)
Keywords: Philosophie islamique

المؤتمر الرابع للدراسات الإباضية (الفقه الإباضي)2013/05/27 - 2013/05/31 Poland, Krakow قراءة في أبرز محطاته البحثية - الإسماعيلي, أحمد (التفاهم, 2013)
Keywords: Fiqh

Diagnostic pour l’identification de stratégies de pérennisation des oliviers millénaires de Djerba, Tunisie - Wehbe, N. (Université libanaise, 2013)
Keywords: Agriculture -- Djerba

Virginie PRÉVOST, L’aventure ibāḍite dans le Sud tunisien. Effervescence d’une région méconnue, Helsinki, Academia Scientiarum Fennica, 2008, 479 p. - Amara, Allaoua (Studia Islamica, 2013)
Keywords: Recension

Inquisition in early Islam: the competition for political and religious authority in the Abbasid empire - Turner, John P. (Library of Middle East history, 2013)

Abū Yazīd al-Nukkārī - Chapoutot-Remadi, Mounira (Encyclopaedia of Islam, 2013)
Keywords: Biographies; Ibn Kaydad; Nukkarisme

Bughtūrī, Maqrīn al- - Prevost, Virginie (Brill, 2013)
Keywords: Biographies -- Djebel Nefousa

Sortir du face-à-face colonial : circulations et projections des lettrés mozabites, 1920-1950 - Jomier, Augustin (Histoire de l’Algérie coloniale Longue durée et désenclavement, 2013)
Keywords: Réformisme -- Mzab

Islamic Reform and Arab Nationalism. Expanding the Crescent from the Mediterranean to the Indian Ocean (1880s-1930s) - Bang, Anne K. (Journal of Islamic Studies, 2013)
Keywords: Recension

Muslims, Scholars, Soldiers: The Origin and Elaboration of the Ibadi Imamate Traditions * By ADAM GAISER. - Salimi, Abdulrahman al- (Journal of Islamic Studies, 2013)
Keywords: Recension

Note sur l'entrée d'Alger sous la souveraineté ottomane (1519-1521) - Vatin, Nicolas (Turcica, 2013)

Laylà bint Tarif's Rita' : An exemple of Kharijite Female Poetry - Masullo, Mariangela (Islam and globalisation: historical and contemporary perspectives: proceedings of the 25th Congress of L'Union Européenne des Arabisants et Islamisants, 2013)
Keywords: Kharijisme

Tower-Fortresses of Ancient Magan: A study of the tower-fortresses of the third millenium on the Oman Peninsula - Botan, Sam A. (Leiden University, 2013)
The tower-fortress on the Oman Peninsula have always been a mystery to archeologists. A total of 15 tower-houses have been excavated or surveyed by archeologists in the past decades and yet their purpose inside the settlements is still poorly understood. This thesis analyzes and evaluates the existing theories about the tower-houses and offers an alternative theory by taking into account the locations, sizes and construction techniques of these buildings, using the survey and excavation rapports. The origins of the tower-fortresses can be found as early as the end of the fourth millennium B.C., when the settlement pattern on the Oman Peninsula shifts from the coast to the hinterland. The shift from the coast to the oasis brought a diversification of resources as well as a tighter appropriation of space. Combined with an increase in the copper trade at the beginning of the third millennium, this induced more complexity in the social system. The form of social organization which emerged on the Oman Peninsula due to these factors, was one which was in a liminal stage between a chiefdom and a state society, called a stratified non-state society. The tower-fortress of the Oman Peninsula functioned in such a society as dwellings and locus of regional power of a particular family or moiety. The few towers that have been excavated show many similarities, such as: he positioning of the towers within the settlements, the usage of a platform on which the towers rest, the interior of the platform consisting of two rows of chambers divided by a corridor or well, the ditches surrounding the towers and thus separating them from the rest of the settlement, the fact that all of the towers could only have been accessed by a ramp, etc. All of these similarities indicate specialization and one has to wonder if the possibility exists of a specialized class of tower-builders, travelling from settlement to settlement
Keywords: Archéologie -- Oman

Fitilin Ucunda Tersane-yi Âmire - Gürkan, Emrah Safa (İstanbul 29 Mayıs Üniversitesi; İstanbul Büyükşehir Belediyesi Kültür A.Ş., 2013)
Akdeniz’in iki yakasında birbirlerine paralel bir şekilde bölgesel bir güç olarak ortaya çıkan Osmanlılar ve Habsburglar 16. yüzyıl boyunca sürecek esaslı bir emperyal rekabete girişecek ve peşlerinden dönemin diğer siyasi ve askeri aktörlerini de sürükleyerek bir cihan hakimiyeti kavgası vereceklerdi. Her ne kadar Türkçe tarih yazımında bu rekabetin Akdeniz ayağı gerek dil engelleri, gerekse kaynakların eksikliği nedeniyle ihmal edilmişse de Osmanlılar ve Habsburglar’ın kozlarını sadece Macaristan ovasında değil, aynı zamanda Akdeniz sularında da paylaştığı unutulmamalıdır.

Le rachat de captifs espagnols à Alger au XVIe siècle. Le cas de la rédemption de Diego de Cisneros (1560-1567) - Chaulet, Rudy; Ortega, Olga (Cahiers de la Méditerranée, 2013)

Early Ibāḍī Theological Arguments on Atoms and Accidents - Salimi, Abdulrahman al- (Arabic Sciences and Philosophy, 2013)
Le gros de la recherche orientaliste consacrée à la littérature théologique islamique a négligé les idées théologiques Ibāḍī à portée cosmologique, ce qui a conduit à une compréhension incomplète de la théologie islamique et à un manque considérable dans la recherche occidentale. L'omission de ce mouvement important de l'Islam est compréhensible étant donné que les textes Ibāḍī ne sont accessibles, publiés, diffusés et traduits que de façon très partielle. Cette étude vise donc à combler certaines de ces lacunes dans la recherche sur la première théologie islamique. Les objectifs de cet article sont de: 1) caractériser la littérature Ibāḍī classique portant sur la théorie atomiste de la substance et de l'accident; 2) examiner les textes d'auteurs Ibāḍī du iiie/ixe siècle dialoguant et discutant avec d'autres écoles théologiques islamiques, à savoir les Muʿtazilites pré-Bahshamiyya (Abū Hāshim al-Jubbāʾī, d. 321/933) et les Ashʿarites (Abū al-Ḥasan al-Ashʿarī, d. 324/936), en lien avec la théorie atomiste de la substance et de l'accident; 3) passer en revue le grand nombre d'opinions soutenues parmi les premiers théologiens Ibāḍī, et examiner les sources et les thèmes spécifiques susceptibles d'avoir influencé cette école de pensée diversifiée. Cet article cherche aussi à identifier des traits communs dans l'approche Ibāḍī durant la période de formation de la théologie islamique, et à explorer les voies grâce auxquelles ces premiers théologiens ont pu avoir accès à des thèmes cosmologiques antérieurs à l'Islam.

L'Aventure Ibadite dans le Sud Tunisien: Effervescence d'une région méconnue (VIIIe-XIIIe siècle) - Ghazal, Amal N. (Der Islam, 2013)
Keywords: Nukkarisme; Recension

Slaves and Silver across the Strait of Gibraltar: Politics and Trade between Umayyad Iberia and Khārijite North Africa - Gaiser, Adam R. (Medieval Encounters, 2013)
berian Umayyad relations with the Ibāḍī Rustumids and the Ṣufrī Midrārids have not been well understood. After an initial period of Khārijite rebellion against the Umayyads in the 120s/740s, in which Khārijite revolutions in North Africa spilled over into the Iberian Peninsula, profound ties developed between the Umayyad amīrs, and the Midrārid and Rustumid imāms. In the far Maghrib, where ‘Abbāsid power did not reach, trade—especially the trade in human beings—brought these erstwhile political and religious enemies together. Relationships between these groups lasted well beyond the destruction of the Midrārid and Rustumid dynasties in the early fourth/tenth century. This paper re-examines the textual and numismatic evidence for Ibāḍī, Ṣufrī, Iberian Umayyad (and even early ‘Abbāsid) relations in order to propose that strong economic interests based primarily in the slave trade underlay the political ties that developed in the late second/eighth century between these groups.
Keywords: Esclavage -- Afrique du nord

The Essentials of Ibāḍī Islam, by Valerie J. Hoffman - Salimi, Abdulrahman al- (Ilahiyat studies, 2013)
Keywords: Recension

Water and tribal settlement in South-East Arabia: a study of the Aflāj of Oman - Wilkinson, John Craven (Studies on Ibadism and Oman, 2013)
Keywords: Géographie -- Oman

The Ibadis in the region of the Indian Ocean. Sect. 1: East Africa - Gaube, Heinz (Studies on Ibadism and Oman, 2013)
Keywords: Ibadisme -- Afrique de l'Est

A Political Culture and Foreign Policy Shaped by a Moderate Religious View: The Case of the Sultanate of Oman - Rabi, Uzi (Oman and overseas, 2013)
Keywords: Vie politique -- Oman -- 1970-2020

The South East European View - Ziaka, Angeliki (Oman and overseas, 2013)

Historical Coincidences between Oman and Brazil: Portuguese Invaders, African Slaves and the Majlis al-Jinn - Pacheco, Leila M. S. (Oman and overseas, 2013)
Keywords: Esclavage -- Oman

The Seminar für Orientalische Sprachen (SOS) at Berlin: Aspects of the Relationship between Oman and Germany in the Late 19th and Early 20th Century - Hoffmann-Ruf, Michaela (Oman and overseas, 2013)
Keywords: Relations -- Oman -- Allemagne

A Historical Survey of US-Omani Relations from 1790 to the Present - Leonard, Douglas R. (Oman and overseas, 2013)
Keywords: Relations -- Oman -- Etats-Unis

Oman through Jewish Travellers’ Eyes - Schreiner, Stefan (Oman and overseas, 2013)
Keywords: Judaïsme -- Oman; Récits de voyage -- Oman

Danish and Norwegian Travel Accounts of Oman, 1765–1995: Changing Views across Sea and Land - Bang, Anne K. (Oman and overseas, 2013)
Keywords: Récits de voyage -- Oman

African Perspectives - Kusimba, Chapurukha M. (Oman and overseas, 2013)

Mosaic Oman: Views from India - Dietl, Gulshan (Oman and overseas, 2013)

Zanzibar: The Sultanate and the Ottoman State in Africa - Gol, Mohammed Z. (Oman and overseas, 2013)

Oman: The Arab Views - Ghazal, Amal N. (Oman and overseas, 2013)

Oman: The Russian View since the 15th Century - Rezvan, Efim (Oman and overseas, 2013)
Keywords: Récits de voyage -- Oman

Oman and Ibadism in Modern French Historiography: Assessing a Semi-Failure - Dridi, Moez (Oman and overseas, 2013)

The British Historical View of Oman and Ibadism - Worrall, James (Oman and overseas, 2013)

Wood, Horses and Friendship. The Arabic Letters from Muscat to the Dutch in Kochi (1779) and Batavia (1798–1806) - Witkam, Jan Just (Oman and overseas, 2013)

Oman and Omanis in Portuguese Sources in the Early Modern Period (ca. 1500-1750) - Cunha, João Teles e (Oman and overseas, 2013)
Keywords: Relations -- Oman -- Portugal

Omani Trade and Cultural Relations with East Asian Countries - Ziaee, Ali Akbar (Oman and overseas, 2013)
Keywords: Commerce -- Oman

From Slumber to Assertion: Maritime Expansion of the Ibadis of Oman and the Responses of Estado da India,1622–1720 - Malekandathil, Pius (Oman and overseas, 2013)

The Formation of Oman’s Maritime Power under the Yaariba and Sayyid Said - Staples, Eric (Oman and overseas, 2013)

The Growth of the Relationships between Oman, the Gulf and the Western Waters of the Indian Ocean. Oman: The Corner-Stone of a Maritime System - Piacentini Fiorani, Valeria (Oman and overseas, 2013)

The Portuguese in East Africa and the Omani Reconquest of East Africa - Newitt, Malyn (Oman and overseas, 2013)
Keywords: Relations -- Oman -- Portugal

The Main Languages of East Africa and their Literatures - Bakari, Mohammed Ali (Oman and overseas, 2013)
Keywords: Littérature -- Zanzibar

Ibadis in East Africa: Archaeological and Historical Evidence - Horton, Mark (Oman and overseas, 2013)
Keywords: Archéologie -- Zanzibar

The Swahili Coast: Africa’s Window on the Indian Ocean - Sheriff, Abdul Mohamed Hussein (Oman and overseas, 2013)

Omani Seafaring and Omani Boat - Vosmer, Tom (Oman and overseas, 2013)
Keywords: Archéologie -- Oman

Umani Ports in Chinese Sources - Kauz, Ralph (Oman and overseas, 2013)

Omani Seafaring Identity before the Early 1600s: Ethnic and Linguistic Diversity - Agius, Dionisius A. (Oman and overseas, 2013)
Keywords: Navigation -- Oman

The Origins of Omani Identity - Wilkinson, John Craven (Oman and overseas, 2013)

Late pre-Islamic Oman: The Inner Evidence – The Outside View - Yule, Paul A. (Oman and overseas, 2013)
Keywords: Archéologie -- Oman

Djerba and the Limits of Rustamid Power. Considering the Ibāḍī Community of Djerba under the Rustamid Imāms of Tāhert (779-909CE) - Love Jr, Paul M. (Al-Qantara : Revista de Estudios Arabes, 2013)
This article is aimed at analyzing the medieval and modern source material dealing with the history of Djerba under the Rustamid Imāmate in an attempt to clarify the nature of both the historical and historiographical relationship between them. It will begin by discussing the available primary and secondary source material, including the historiographical challenges they present. An analysis of the textual and archeological evidence connecting the Rustamids and Djerba will follow. Next, it will attempt to synthesize the scattered bits of evidence available in the historical record in an effort to present a clearer picture of Djerba in the Rustamid period. On the basis of this textual and archeological evidence, it will be argued that Djerba was home to an ibādī community independent of the government in Tahert for the majority ‒if not all‒ of that Imāmate’s existence ‒distinguishing the island from the surrounding areas of the Djerid (in southern Tunisia), parts of Aghlabid Ifrīqiya and the Jebel Nafūsa. Furthermore, it will be shown that evidence suggests this independence was not only a political, but also a religious one. Este ensayo analiza las fuentes de origen medieval y moderno sobre la historia de Ŷarba en el Imāmato rustamí en un intento de aclarar la naturaleza de la relación histórica e historiográfica entre ellos. Se empieza por discutir las fuentes primarias y secundarias disponibles, incluyendo los retos historiográficos que plantean y se presenta a continuación un análisis de las evidencias textuales y arqueológicas que conectan a los rustamíes con Ŷarba. Se intenta después sintetizar las piezas dispersas de la evidencia disponible en el registro histórico con el fin de presentar una imagen más clara de Ŷarba durante el período rustamí. Con base en esta evidencia textual y arqueológica, se argumentará que Ŷarba era hogar de una comunidad ibādí independiente del gobierno en Tāhert durante la mayor parte (si no en su totalidad) de la existencia del Imāmato, distinguiendo así la isla de los alrededores del Ŷarid (en el sur de Túnez), partes de la Ifrīqiya Aglabí y el Ŷabal Nafūsa. Se muestra por último que la evidencia sugiere que esta independencia no era solamente política, sino religiosa.
Keywords: Monuments -- Djerba; Tâjdît, Mosquée (Fâtû, Djerba)

Les fortifications de l'île de Djerba : enjeux doctrinaux et stratégies méditerranéennes (Xe-XVIe siècles) - Hbaieb, Mohamed Ali (Fortificações e território na Península Ibérica e no Magreb: séculos VI a XVI, 2013)
Keywords: Bardawi, mosquée al- (Mezrane, Djerba); Monuments -- Djerba

Nourritures médiévales: L'alimentation au maghreb d'après les sources ibadites (xie-xiiie siècle) - Prevost, Virginie (Travelling through time: essays in honour of Kaj Öhrnberg, 2013)
Keywords: Alimentation -- Afrique du Nord

Ibadhi Jerba and its Pattern of Settlement - Holod, Renata (Lecture, Seminar and Book Workshop, 2013)
Keywords: Urbanisme -- Djerba

Similitudes et différences dans l’architecture vernaculaire domestique et religieuse d’un même groupement humain (Les berbères) dans deux contextes géographiques différents. (Cas de l’architecture vernaculaire de l’ile de Djerba et les montagnes de Matmata, Demmer et Nafousa en Libye) - Ben Younes, Houda (Ecole Nationale d’Architecture et d’Urbanisme de Tunis, 2013)
Keywords: Architecture -- Djerba

Assessment of the effect of modern transformation on the traditional settlement ‘Ksar’ of Ouargla in southern Algeria - Sebti, Moufida; Alkama, Djamel; Bouchair, Ammar (Frontiers of Architectural Research, 2013)
Keywords: Architecture -- Mzab

Anatomy of dissent in Islamic societies: Ibadism, rebellion, and legitimacy - Souaiaia, Ahmed E. (Palgrave Macmillan, 2013)

Habitat semi-collectif à Midoun Djerba - Belhassine, Ridha (Ecole Nationale d’Architecture et d’Urbanisme de Tunis, 2013)
Keywords: Architecture -- Djerba

Maisons de l'île de Djerba - Azzouz, Ashraf; Jabeur, Salah (Dar Ashraf Editions, 2013)
Keywords: Architecture -- Djerba

Para una biografía de Lope de Figueroa : notas críticas y nuevas aportaciones. Parte primera: hasta la jornada de Djerba y el final de su cautiverio por los Turcos (1564) - Leonardi, Salvatore (Revista de historia militar, 2013)
Keywords: Invasions chrétiennes -- Djerba -- 1560

The Threat of Liberation: Imperialism and Revolution in Zanzibar - Wilson, Amrit (Pluto Press, 2013)
The Threat of Liberation returns to the tumultuous years of the Cold War, when, in a striking parallel with today, imperialist powers were seeking to institute ‘regime change’ and install pliant governments.Using iconic photographs, declassified US and British documents, and in-depth interviews, Amrit Wilson examines the role of the Umma Party of Zanzibar and its leader, the visionary Marxist revolutionary, Abdulrahman Mohamed Babu. Drawing parallels between US paranoia about Chinese Communist influence in the 1960s with contemporary fears about Chinese influence, it looks at the new race for Africa’s resources, the creation of AFRICOM and how East African politicians have bolstered US control. The book also draws on US cables released by Wikileaks showing Zanzibar's role in the ‘War on Terror’ in Eastern Africa today.The Threat of Liberation reflects on the history of a party which confronted imperialism and built unity across ethnic divisions, and considers the contemporary relevance of such strategies.
Keywords: Zanzibar

Le M’zab : de la pentapole à la métropole - Maachou, M. (Bulletin des sciences géographiques, 2013)
Keywords: Urbanisme -- Mzab

Nalut al-jihad min al-ajdad ila ahfad - Bin Dilla, Muhammad (Dar al-kutub al-wataniyya, 2013)
Keywords: Vie politique -- Djebel Nefousa

Libyan Berber Heritage: Jefara, Adrar Nafusa and Hamada al Hamra Cultural Landscapes. A possible new Tentative Candidate for UNESCO List - Bencini, Claudio (Fondazione Onlus, 2013)
Libyan Berber Heritage: Jefara, Adrar Nafusa and Hamada al Hamra Cultural Landscapes. A possible new Tentative Candidate for UNESCO List
Keywords: Archéologie -- Djebel Nefousa

Etude d’un cas d’aménagement touristique, zone de Cheikh Yahia-Sidi Jmour, île de Djerba - Keskes, Dhouha (Facultés Des Sciences de Tunis, 2013)
Keywords: Tourisme -- Djerba

Girba, la princesse fugitive - Tmarzizet, Kamel (STAG, 2013)
Keywords: Littérature -- Djerba

Comme un arc-en-ciel, recueil de poèmes - Guellouz, Souâd (Arabesques, 2013)
Keywords: Littérature -- Djerba

Jespersen’s Cycle in Libyan Arabic and Nafusi Berber - Ghadghoud, Khawla (University of Manchester, 2013)
Keywords: Linguistique -- Djebel Nefousa

The Birds of Djerba - Torres-Recinos, Julio (Cloudburst: an anthology of Hispanic Canadian short stories, 2013)
Keywords: Littérature -- Djerba

La valorisation du patrimoine immatériel juif de Djerba - Hammi, Yosr (Institut Supérieur des Métiers du Patrimoine de Tunis, 2013)
Keywords: Architecture -- Djerba

Negotiating the Future, observations and visions of urban phenomena in Djerba - Salheen, Mohamed (IUSD Ain Shams University, 2013)
Keywords: Architecture -- Djerba

Etude de la commune de Guellala à Djerba (Tunisie) : une des dernières localités berbères - Hadjam, Aoussia (Université Paris 8, 2013)
Keywords: Linguistique

L'Afrique occidentale: Algérie, Mzab, Tildikelt - Soleillet, Paul (El Kalima, 2013)
Keywords: Récits de voyage -- Mzab

Le Corbusier: albums d'Afrique du Nord, voyages au M'Zab, 1931 et 1933 - Pauly, Danièle (Archives d'architecture moderne, 2013)
"A l'occasion des voyages qu'il fit en Afrique du Nord, en août 1931 et en mars 1933, Le Corbusier utilisa, outre ses habituels carnets de poche, deux grands albums à spirale, recouverts d'une couverture cartonnée grise. Ceux-ci sont - avec l'album "La Roche" et avec les deux albums de l'arrivée à Paris en 1917 - les plus précieux dans le corpus détenu à la Fondation Le Corbusier. Ils renferment des dessins caractéristiques de la production la plus heureuse de l'artiste, celle des années trente. Au fil des pages, se succèdent scènes de genre saisies dans des villages marocains, portraits de femmes mauresques, nus féminins, paysages de la baie d'Alger ou de la côte marseillaise, esquisse d'implantation d'un projet pour la capitale algérienne, vues aériennes prises dans le désert saharien; et enfin, de nombreux croquis faits au M'Zab où l'architecte découvre avec stupeur, émotion et enthousiasme une civilisation inattendue, vieille de mille ans, dans l'oasis de Ghardaïa"
Keywords: Architecture -- Mzab

Le M'Zab - Benhassir, Smail; Seddiki, Hocine (Albayazîn, 2013)

Emblèmes territoriaux et attachement aux origines : le cas des communautés djerbienne et gafsienne à Morneg - Kdhai, Houda (Penser la société tunisienne aujourd'hui: la jeune recherche en sciences humaines et sociales, 2013)
Keywords: Emigration -- Djerba

Djerbian Talmudic Commentary: "Terumat HaDeshen" by R. Tzemach Cohen / פרשנות ג'רבאית לתלמוד: "תרומת הדשן" לר' צמח כהן - ארנד, אהרן; Arend, Aharon (Sidra: A Journal for the Study of Rabbinic Literature / סידרא: כתב-עת לחקר ספרות התורה שבעל-פה, 2013)
Keywords: Judaïsme -- Djerba

Le culte de la Maâmoura dans l’île de Djerba - Boukamcha, Souhaiel (Institut Supérieur des Métiers du Patrimoine de Tunis, 2013)
Keywords: Croyances populaires -- Djerba

Neotectonics of Jerba, Zarzis and Jorf (southern Tunisia): A pull-apart on a NW-SE right lateral transtensive fault zone - Ghedhoui, Rim; Deffontaines, Benoît; Rabia, Mohamed Chedly; Zetrini, H. (The 5th Tunisian Days of Applied Geology JTGA 2013, 2013)
Keywords: Géologie -- Djerba

Étude hydrochimique et géochimique de la nappe profonde Mio-Pliocene de l’île de Djerba - Farhat Mansour, S.; Kallel, M. (The 5th Tunisian Days of Applied Geology JTGA 2013, 2013)
Keywords: Géologie -- Djerba

Petroleum Prospectivity of the Jurassic Strata of the Jeffara Basin, Tunisia - Haddad, S.; Echihi, O.; Ben Jemia, H. (2013)
Keywords: Pétrole -- Djebel Nefousa

Distributed Renewable Energies for Off-Grid Communities - El Bassam, Nasir; Maegaard, Preben; Schlichting, Marcia Lawton (Elsevier, 2013)

Contribution des SIG à la gestion intégrée des ressources en eaux dans la région de Djerba - Ben Maiz, Amir (Faculté des Sciences Mathématiques, Physiques et Naturelles de Tunis, 2013)

Obésité morbide chez les enfants d’Age scolaire dans la région de Djerba. Etude de la prévalence et des facteurs de Risque - Selmi, Ines (Faculté de Médecine de Tunis, 2013)
Keywords: Médecine -- Djerba

The Jerba island (Tunisia) through a demo-genetic study - Mourali, Soufia; Heyer, Evelyne; Benammar Elgaaied, Amel; Langaney, André (2013)
Keywords: Génétique -- Djerba

Diversité spécifique de la macrofaune benthique dans la côte ouest de la baie de Tunis et la côte de l’île de Djerba (sud-ouest de la Méditerranée) - Afli, Ahmed (Bulletin de l’Institut National des Sciences et Technologies de la Mer, 2013)
Keywords: Biologie -- Djerba

Les articulations de l’Afrique Mineure dans le Périple dit de Scylax - Cheyns, André; Isebaert, Labert; Mund-Dopchie, Monique; Desanges, Jehan (Heureux qui comme Ulysse: hommage à Monique Mund-Dopchie, 2013)
Les recherches scientifiques du Monique Mund-Dopchie, à qui ce volume rend hommage, s'articulent autour de trois axes essentiels : la survie des tragiques grecs à la Renaissance; la représentation, dans l'imaginaire antique, des régions situées aux confins du monde; la réception des récits de voyage grecs et latins à l'époque des Grandes Découvertes. C'est cette dernière orientation que les éditeurs ont privilégiée en organisant un colloque sur le "Voyage dans l'Antiquité grecque", afin d'illustrer quelques-uns des thèmes majeurs qui traversent l'oeuvre scientifique du Pr Monique Mund- Dopchie: la découverte de l'inconnu, l'attrait du lointain et la rencontre de l'Autre. La première partie de cette publication réunit quatre communications portant, d'abord sur le Voyage, et plus particulièrement sur les errances d'Ulysse
Keywords: Archéologie -- Djerba

Arab-Berber contacts in the Middle Ages and ancient Arabic dialects: new evidence from an old Ibāḍite religious text - Brugnatelli, Vermondo (African Arabic: Approaches to Dialectology, 2013)
L’analyse d’un long manuscrit contenant un texte arabo-berbère du Moyen Âge, le Kitāb al- barbariyya, connu aussi sous le nom de Moudaououana d’Ibn R’anem (Motylinski et Bossoutrot) ou Mudawwana d’Abû Ġânim al-Ḫurâsânî (Ould-Braham et U-Madi), permet de relever quelques phénomènes liés au contact linguistique entre le berbère et l’arabe du Moyen Âge. La date de composition du texte n’est pas connue mais elle remonte à une époque assez reculée (entre le 10ème et le 15ème siècle). Plusieurs indices (entre autres, l’orthographe du son [g], transcrit avec <ǧ> et pas avec <q>) font penser à une période antérieure ou très proche de l’invasion hilalienne. Parmi les phénomènes observables, on notera : - d’un côté les emprunts du berbère à l’arabe, qui sont concentrés surtout dans le domaine de la religion, même si la langue du document préserve beaucoup de lexique indigène. Dans quelques cas, on peut constater une évolution dans l’utilisation des emprunts d’un livre à l’autre à l’intérieur de l’ouvrage, probablement en raison d’une différence d’époque de composition des différentes parties ; - de l’autre côté, dans certains cas, comme les noms de nombre de la deuxième dizaine, la forme de l’emprunt démontre une évolution déjà avancée de la langue arabe parlée au Maghreb par rapport à la langue « classique ».
Keywords: Linguistique -- Djebel Nefousa

Peintures romaines de Tunisie - Barbet, Alix (Picard, 2013)
Ce livre, fruit d'un long et patient travail de recherche, rassemble les vestiges des décors d'une vingtaine de sites majeurs de Tunisie. Il nous révèle des peintures de grande qualité et d'une grande variété revêtant aussi bien les murs et plafonds des maisons ou des villas particulières que les thermes publics, les temples, les lieux de spectacles et les nécropoles. Les clichés sont présentés à côté de dessins de restitutions et les rapprochements avec des ensembles plus complets de l'Empire romain revèlent des thèmes tout à fait exceptionnels.
Keywords: Antiquité; Archéologie -- Djerba

التواصل العماني المغربي الحديث: رحلة سليمان باشا الباروني إلى عمان نغوذجا (1940-1924) - الصقري, سعيد بن عبد الله (مجلة دراسات, 2013)
Keywords: Bārūnī, Sulaymān al- (1870-1940)

al-qaṣīda al-ʿumāniyya fī riḥlat al-Bārūniyya - Ṭāʼī, ʻĪsá ibn Ṣāliḥ al-ʻUmānī (Muʾassassa al-Ruʾya lil-Ṣaḥāfat wa’l-Nashr, 2013)
Keywords: Bārūnī, Sulaymān al- (1870-1940)

المرحلة العُمانية في حياة الشيخ سليمان الباروني (1924 ـ1940م) - عباس, علي حمزة (مجلة ابحاث كلية التربية الاساسية, 2013)
Keywords: Bārūnī, Sulaymān al- (1870-1940)

تطور الدور التجاري لجزيرة جربة خلال العصر الوسيط - بن غازي, البشير (الحياة الثقافية, 2013)
Keywords: Commerce -- Djerba